خطاب الرحلة والإسلام الأباضى خلال العصر الوسيط والفترة الحديثة - المريمي, محمد (الرحلة والغيرية, 2008)

وثيقة شعرية أمازيغية ترجع لسنة 1881م - ؤمادي, موحمد (سلسلة دراسات النفوسية, 2008)

La Sicile et l'espace libyen au moyen âge - Bresc, Henri (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 2008)
Keywords: Commerce -- Djerba -- 14e siècle; Emigration -- Sicile -- Djerba; Esclavage -- Malte; Esclavage -- Sicile; Navigation -- Djerba; Occupation normande -- Djerba -- 1135-1153

Ibadytska krytyka shyizmu: otsinka khalifatu Abu Bakra - Radivilov, Danylo (The Oriental Studies, 2008)

Політична доктрина ібадитів: "праведні" халіфи = ibādi political doctrine: the ‘righteous' caliphs - Radivilov, Danylo (The World of the Orient, 2008)

أساليب التوكيد في شعر الخوارج - برجس, محمد هلال; محمود, نشأت علي (مجلة ابحاث كلية التربية الاساسية, 2008)
يكشف هذا البحث عن كثرة المؤكدات في شعر الخوارج ،وقد جمعنا كل انماط التراكيب والالفاظ التي تفيد التوكيد الواردة في هذا الشعر، لبيان الاساليب المختلفة المستعملة فيه، ولبيان انواع المؤكدات وانماطها المختلفة…
Keywords: Poésie kharijite

Moufdi Zakaria (1908-1977) - Bendamèche, Abdelkader (Les grandes figures de l'art musical algérien, 2008)
Keywords: Biographies

L'Arabe du coin - Roux De Bézieux, Alexis; Henriot, Thomas (Dilecta, 2008)
Les épiciers sont plus que de simples commerçants. Dépanneurs de l'essentiel, ils offrent également à leurs clients leur bienveillance. C'est cette réalité que les auteurs ont souhaité livrer dans cet ouvrage, en réunissant des paroles, des images prises sur le vif, des témoignages vivants, des rencontres authentiques et émouvantes... Ce livre, préfacé par Eric-Emmanuel Schmitt et illustré par quelque 90 photographies, fait le portrait d'une dizaine de ces personnalités au parcours atypique, et rend hommage à ces hommes et femmes qui, sous l'appellation familière d'" Arabe du coin ", offrent dans leur univers chaleureux un coin d'humanité.
Keywords: Commerce -- Djerba

طرابلس: ملتقى أوروبا و بلدان وسط إفريقيا 1500 - 1795 إفرنجي - Zeltner, Jean-Claude (اللجنة الشعبية العامة للثقافة و الأعلام, 2008)

المؤرخون الليبيون في القرن التاسع عشر دراسة في الثقافة والمنهج - الباشا, عفاف احمد (دار المدار الاسلامي, 2008)

‏حديث القرى - هيبه, عمر بن باحمد (المطبعة العربية, 2008)
Keywords: Poésie -- Mzab

Sultan in Oman - Morris, Jan (Eland, 2008)
Keywords: Récits de voyage -- Oman

حوار بين السنة والإباضية والشيعة - طوطاوي, عبد الرزاق (مكتبة مسقط, 2008)

حفريات موسم 2006 في موقع بوشر سلطنة عمان : دور الموقع و المصادر الطبيعية في نشأة المستوطنات - البلوشي, محمد بن علي (أدوماتو, 2008)
Keywords: Archéologie -- Oman

محنة نفوسة: رجال من جبل نفوسة حولوا المحنة منهة - بابا عمي, محمد بن موسى (ثريا للنشر والتوزيع, 2008)
Keywords: Vie intellectuelle -- Djebel Nefousa

أيام جربة و أهاليها - الرايس, فؤاد (سمباكت, 2008)
Keywords: Ammi Yathi, mosquée (Fahmine, Djerba); Banna, mosquée al- (Guellala, Djerba); Basi, mosquée al- (Oualegh, Djerba); Fadhloun, mosquée (Midoun, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Layl, mosquée al- (Oued Zbib, Djerba); Luta, mosquée (Sedouikech, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Saturi, mosquée al- (Sedouikech, Djerba); Sidi Ibrahim al-Jumni, mosquée (Houmt Souk, Djerba); Sidi Salim, mosquée (Khanfus, djerba); Sidi Zayid, mosquée (Houmt Souk, Djerba); Tourisme -- Djerba; Turuk, mosquée al- (Houmt Souk, Djerba)

العقل بين جماع الطبع وترويض الشرع - الخليلي, أحمد بن حمد (مكتب الإفتاء, 2008)

Khor Rori, Sumhuram - Avanzini, Alessandra (Office of the Advisor to His Majesty the Sultan for Cultural Affairs, 2008)
Keywords: Archéologie -- Oman

Nanorrhinum roseiflorum (Scrophulariaceae), a new species from Dhofar, Southern Oman - Mosti, Stefano; Raffaelli, Mauro; Tardelli, Marcello (Webbia, 2008)
Nanorrhinum roseiflorum, characterized by pink flowers, a twiggy shrub habit and very small leaves, is described as a new species from Dhofar (Oman). it is distributed on the mountain rocky slopes of Jabal Qara, from Qaftwat to Wanat, at an altitude of 900–1150 m, and in the dry area of Wadi Andur, behind Jabal Samhan, at an altitude of 600 m.
Keywords: Botanique -- Oman

Apocynaceae of Oman: Orbea nardii, sp. nov. and Pentatropis bentii, first finding - Raffaelli, Mauro; Mosti, Stefano; Tardelli, Marcello (Webbia, 2008)
Orbea nardii, a new species found in the mountains of Al Mughsayl (central Dhofar, Oman) is here described and compared with some other closely related species of Orbea. Moreover the presence of Orbea luntii in Dhofar is confirmed on the basis of its finding on the southern slope of Jabal Samham and, finally Pentatropis bentti, found in the mountains of Hasik, eastern Dhofar, is recorded for the first time.
Keywords: Botanique -- Oman

Botanical and chemical characterization of frankincense resin from Dhofar - Ribechini, Erika; Raffaelli, Mauro; Colombini, Maria Perla (A port in Arabia between Rome and the Indian Ocean: 3rd C.BC-5th C.AD, 2008)
Keywords: Botanique -- Oman

Scientific activity in Dhofar (2000 - 2004): botanical mission of Florence University - Raffaelli, Mauro; Tardelli, Marcello; Mosti, Stefano (A port in Arabia between Rome and the Indian Ocean: 3rd C.BC-5th C.AD, 2008)
Keywords: Botanique -- Oman

المطبعة العربية: محلم وطني مجهول 1931-1962 - ناصر, محمد صالح (مكتبة الريام, 2008)

حي على الصلاة (مؤسسة الشيخ عمي سعيد, 2008)
Keywords: Fiqh; Fiqh -- prières

العقيدة: القضية الكبرى في حياة البشر - كسكاس, عاشور يوسف (وزارة الأوقاف والشؤون الدينية, 2008)

جهاد الليبيين ضد الغزو الإيطالي من خلال الوثائق الإنجليزية: أحمد الشريف، رمضان السويحلي، 1911-1920 - السويحلي, صلاح الدين عوض (ملامح الجهاد الليبي, 2008)
Keywords: Invasion italienne -- Libye; Sources

منهج الشيخ بيوض في الإصلاح والدعوة - بوحجام, محمد بن قاسم ناصر (جمعية التراث, 2008)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Réformisme -- Mzab

العزابة ودورهم في المجتمع الإباضي بميزاب - اسماوي, صالح بن عمر (مطبعة الفنون الجميلة, 2008)
Keywords: Vie religieuse -- Mzab

عقيدتي - الهنائى, سلطان بن سعيد (المؤلف, 2008)
Keywords: Foi -- Traité -- 2000-....

زيغ: العقيدة من خلال الشعوذة - بيوض, عمر سليمان (المؤلف, 2008)

أسواق الأوراق المالية وضوابطها في النظر الفقهي - الكندي, ماجد بن محمد (وزارة الأوقاف والشؤون الدينية, 2008)

رأي على رأي: ردا على كتاب معجم الفرق والنحل في الجزائر لمؤلفه عبد القادر بوعرفة - صدقي, محمد بن ايوب (المؤلف, 2008)

الحق الدامغ - الخليلي, أحمد بن حمد (دار الحكمة, 2008)
Keywords: Polémique

Khawarij and Ibadiyya - Abderrazzaq, Mohammad A. (The Oxford Encyclopedia of the Modern World, 2008)
"Khawarij and Ibadiyya" published on by Oxford University Press....
Keywords: Kharijisme

مختصر الخصال تألیف الإمام إبراھیم بن قیس الھمداني الحضرمي من علماء القرن الخامس الھجري : دراسة وتحقیق - الخروصي, عبد الرحمن بن محمد بن نبھان (جامعة آل البيت, 2008)
Keywords: Fiqh -- Oman -- 11e siècle

تجديد الفقه وتيسيره - الشعيلي, خلفان بن سنان (أعمال ندوة تطور العلوم الفقهية - التقنين والتجديد في الفكر الإسلامي المعاصر, 2008)

حركة المطرّف بن المغيرة بن شعبة وأثرها على النظام الأموي في النصف الثاني من القرن الأول الهجري (76 هـ / 695 م - 78 هـ / 697 م) - الشياب, شهاب علي (المجلة الأردنية للتاريخ والآثار, 2008)

وصية الأقرب عند الإباضية وآراء المذاهب الفقهية: دراسة تأصيلية ومقاصدية - الهنداز, معز (جامعة الزيتونة, 2008)

موقف الإمامة الإباضية من الصراع القرمطى البويهى على عمان 287 هـ. / 900 م. - 447 هـ. / 1055 م. - الوهيبى, يوسف بن محمد بن حميد (جامعة السلطان قابوس, 2008)

حرية الإشتراط فى العقود فى الفقه الإسلامى المقارن - باجو, مصطفى بن صالح (مجلة جامعة الأمير عبد القادر للعلوم الإسلامية, 2008)

نشاط الحركة المذهبية الخارجية ببلاد المغرب الإسلامي خلال القرن الرابع الهجري : ثورة أبي يزيد الخارجي نموذجا - بلهواري, فاطمة (مجلة المواقف, 2008)
Keywords: Ibn Kaydad

تبغورين الملشوطي وآراؤه الكلامية من خلال كتابه أصول الدين - سالم, محمد (جامعة الزيتونة, 2008)
Keywords: Foi -- Traité -- 12e siècle; Malshūṭī, Tibghūrīn b. ʿĪsā al-

Rencontre avec Mgr Fouad Twal - Twal, Fouad (La Terre sainte, 2008)
Keywords: Christianisme -- Djerba

طلعة الشمس :‏ ‏شرح شمس الأصول - السالمي, عبد الله بن حميد (مكتبة الإمام السالمي, 2008)

معجم مصطلحات الإباضية: العقيدة، الفقه، الحضارة - بحاز, إبراهيم بن بكير; السالمي, عبد الرحمان; بابا عمي, محمد بن موسى (وزارة الأوقاف والشؤون الدينية, 2008)

Trucial states: 1959-1962 - Wilkinson, John Craven (Oman and the Trucial states, 2008)

الدعوة والتبليغ مسؤولية المسلمين في العالم: نشأتها – أهدافها – مناهجها - ميتا, خالد زيد (مكتبة مسقط, 2008)

غناء الصوت في جهة تطاوين المقومات الإجتماعية و الحضارية و التعبيرية - حامد, أحلام (المعهد العالى للموسيقى, 2008)

Oralité et nouvelles dimensions de l'oralité: intersections théoriques et comparaisons des matériaux dans les études africaines - Lafkioui, Mena; Merolla, Daniela (Colloques langues O', 2008)
Keywords: Linguistique

المقاربة الانتربولوجية في الموسيقى التونسية والعربية، إشكالية الآليات والاهداف - قوجة, محمد (أنثروبولوجيا الموسيقى، الواقع والآفاق, 2008)

البيئة الصحراوية و أثرها على العمران والعمارة - وادي ريغ نموذجا- - حملاوي, علي (آثار, 2008)
البيئة لفظة شائعة الإستخدام يرتبط مدلولها بنمط العلاقة بينها و بين مستخدمها، كأن نقول "البيئة الصناعية و البيئة الطبيعية " أما مدلولها من وجهة نظر الباحثين و المتفق عليه ان البيئة هي جميع الظروف و العوامل الخارجية التي تعيش فيها الكائنات الحية و تؤثر في العمليات التي تقوم بها .
Keywords: Architecture -- Oued Righ

حمد تيبو تيب ودوره السياسي في وسط أفريقيا - طنش, أحمد محمد (مجلة القادسية في الاداب والعلوم التربوية, 2008)
Keywords: Tippo Tip (1837-1905)

"Sadaqan agilan wa-agilan": Einige Anmerkungen zu Form und Inhalt von Ehedokumenten in Oman - Hoffmann-Ruf, Michaela (Die Grenzen der Welt: Arabica et Iranica ad honorem Heinz Gaube, 2008)

Coins of the Omani Imams during the Buyid Period: Studying the Bahla Hoard - Salimi, Abdulrahman al- (Die Grenzen der Welt: Arabica et Iranica ad honorem Heinz Gaube, 2008)
Keywords: Numismatique -- Oman

Rüstemîler. الرستميّون. Cezayir’de hüküm süren İslâm hânedanı (777-909) - Özkuyumcu, Nadir (İslâm Ansiklopedisi, 2008)
Keywords: Dynastie rustumide

al-Baruni, Za‘ima Sulayman (1910–1976) - Ashour, Radwa; Ghazoul, Ferial; Reda-mekdashi, Hasna (Arab Women Writers: A Critical Reference Guide, 1873-1999, 2008)
Libyan literary pioneer and short-story writer born in Jadu, located in Libya’s western mountains. She is the daughter of anti-colonial fighter Sulayman al-Baruni. She received her early education in Turkish in Istanbul and then returned to Libya, where she completed her studies in the field of Arabic. She witnessed the various phases of her father’s struggle and after his death settled in Tripoli. She worked in education after Libyan independence and published her literary works in Libyan newspapers and magazines. She collected and edited critical editions on her father’s life and poetry. She participated in the Afro-Asian Women’s Conference held in Cairo in 1960.
Keywords: Biographies -- Djebel Nefousa -- 20e siècle

جامع أبي الحسن البسيوي - البسيوي, أبو الحسن علي بن محمد (وزارة التراث والثقافة, 2008)
Keywords: Fiqh -- Oman -- 11e siècle

جامع أبي الحسن البسيوي - البسيوي, أبو الحسن علي بن محمد (وزارة التراث والثقافة, 2008)
Keywords: Fiqh -- Oman -- 11e siècle

جامع أبي الحسن البسيوي - البسيوي, أبو الحسن علي بن محمد (وزارة التراث والثقافة, 2008)
Keywords: Fiqh -- Oman -- 11e siècle

جامع أبي الحسن البسيوي - البسيوي, أبو الحسن علي بن محمد (وزارة التراث والثقافة, 2008)
Keywords: Fiqh -- Oman -- 11e siècle

الصحراء الجزائرية خلال العصر الحجري الحديث (1600 ق.م - 1000ق.م) - جرايه, محمد رشدي (جامعة قسنطينة, 2008)

تحليل سيميائي لقصيدة فلسطين على الصليب لمفدي زكرياء - رخرور, خضرة (جامعة الجزائر 2, 2008)
تحتوى الرسالة على ثلاثة فصول وهي محاولة لتحيل سيميائي لقصيدة فلسطين على الصليب لمفدي زكريا تناول الفصل الأول التجلي الإيقاعي وهو على ثلاثة مباحث الإيقاع الصوتي ثم العروضي ثم إيقاع البياض والسواد أما الفصل الثاني فتناول التجلي التركيبي من خبر وإنشاء وأفعال وتقديم تأخير وصور بلاغية. أما الفصل الثالث فتناول البنية الدلالية بمستويتها المستوى السطحي والمستوى العميق، حيث يقوم المستوى السطحي على المكون السردي والخطابي أما المستوى العميق فيتكون من التشاكلات الدلالية والسيميولوجية وخوالمضمون في المربع السيميائي.
Keywords: Poésie -- Mzab

خواطر حول ما ألت اليه مساجد جربة التاريخية، واضافات لماورد حول البعض منها في مدونة الاستاذ المرابط - بن يحياتن, ساسي بن عمر (Al-Jazira | الجزيرة, 2008)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Monuments -- Djerba; Qasbiyyin, mosquée al- (Guellala, Djerba)

Patrimoine, économie et altérité: essai sur la muséologie des mémoires entre deux rives - Karamti, Yassine (Muséum national d'histoire naturelle, 2008)

أهل الله وخاصته؛ المستظهرون لكتاب الله العزيز بالقرارة (الحياة, 2008)

رسالة من الشيخ سعيد شريفي الشيخ عدون، إلى الإمام الشيخ إبراهيم بن عمر بيوض (مؤرخة بسنة 1376هـ/1956م) (الحياة, 2008)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981)

التوثيق؛ واجب شرعي ومهمة اجتماعية واقتصادية - أبو بكر, صالح بن عبد الله (الحياة, 2008)

السيدات والأوانس، وأوجاع الثامن مارس - الأطرش, نورالدين بن بكير (الحياة, 2008)

إعجاز الهداية في القرآن الكريم - الشيخ بالحاج, عيسى بن محمد (الحياة, 2008)

الأسس الفكرية للنهضة الإصلاحية بوادي ميزاب - الشيخ بالحاج, قاسم بن أحمد (الحياة, 2008)
Keywords: Réformisme -- Mzab

مذكرات البكري «الشيخ عبد الرحمن بن عمر بكلي»(قراءة منهجية) - بابا عمي, محمد بن موسى (الحياة, 2008)

مهرجان القرآن - باجو, صالح بن إبراهيم (الحياة, 2008)

الافتتاحية - باجو, مصطفى بن صالح (الحياة, 2008)

معالم قرآنية لتحقيق ميثاق الوحدة الإسلامية - باجو, مصطفى بن صالح (الحياة, 2008)

مسيرة الإباضية مع القرآن - بحاز, إبراهيم بن بكير (الحياة, 2008)

فهرسة المكتبات والمخطوطات في وادي ميزاب (دراسة وتحليل) - بن دريسو, مصطفى بن محمد (الحياة, 2008)
Keywords: Bibliothèques -- Mzab; Catalogue -- Mzab; Manuscrits -- Mzab

مزاب في العهد العثماني (1510م-1830) - بن عمر, موسى بن بكير (الحياة, 2008)
Keywords: Mzab -- Histoire -- 1510-1830

الهوية في شعر مفدي زكرياء - بوحجام, محمد بن قاسم ناصر (الحياة, 2008)
Keywords: Poésie -- Mzab

يا حافظ القرآن شمر برسالة - بوحجام, محمد بن قاسم ناصر (الحياة, 2008)

مقاربة منهجية للتنظير الفقهي - بوراس, عيسى بن محمد (الحياة, 2008)
Keywords: Fiqh

البدائل الحديثة في استثمار الأوقاف - حدبون, محمد بن قاسم (الحياة, 2008)
Keywords: Waqf (fondations) -- Mzab

الحقائق الحضارية حول كتاب آراء الخوارج الكلامية (دراسة نقدية) - حريزي, موسى بن إبراهيم (الحياة, 2008)

توازن الموازنة العامة، دراسة مقارنة بين الفكر المالي الإسلامي والوضعي - حمدي, محمد بن صالح (الحياة, 2008)

فقه المال العام عند الإباضية (الحلقة الثانية) - حمدي, محمد بن صالح (الحياة, 2008)
Keywords: Fiqh

منهج هود بن محكم الهواري في التفسير - زغيشي, سعاد (الحياة, 2008)
Keywords: Coran -- Commentaires -- 9e siècle; Hawwārī, Hūd b. Muḥkim al-

المحافظون والمجددون في الحركة الإصلاحية الجزائرية... - كعواش, عزيز (الحياة, 2008)
Keywords: Réformisme -- Mzab

وثائق الأرشيف التونسي المتعلقة بجماعة بني ميزاب...(1881-1956) - ناصر, بالحاج بن باحمد (الحياة, 2008)

Affaire des 17 détenus de Ghardaïa - Ait Ouarabi, Mokrane (El Watan, 2008)
Prévu pour hier à la chambre criminelle de la cour de Ghardaïa, le procès de Fekhar Kamal Eddine, secrétaire national du FFS chargé du mouvement associatif, et de ses 16 compagnons ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

« Ils veulent nous briser » - Ait Ouarabi, Mokrane (El Watan, 2008)
L'orage de colère est passé. Ghardaïa retient son souffle, deux semaines après les affrontements ayant eu lieu mercredi 13 octobre entre la population et les forces de l'ordre. Les ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Des crues de l'oued M'zab font 33 morts et 48 blessés : Aïd de deuil à Ghardaïa - Tlemçani, Salima (El Watan, 2008)
Totalement inondée, la vallée du M'zab, à Ghardaïa, n'est aujourd'hui que ruines et désolation. Vingt minutes seulement ont suffi aux pluies diluviennes de mercredi dernier, premier jour de ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

La ville de Ghardaïa a frôlé la catastrophe : Explosion d'une canalisation de gaz de haute pression - Makedhi, Madjid (El Watan, 2008)
Plus de peur que de mal ! Les citoyens de Ghardaïa ont vécu, hier, un début de journée mouvementé. ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Leishmaniose, paludisme, prostitution et suicide des enfants - Tlemçani, Salima (El Watan, 2008)
Pour les touristes de passage, Ghardaïa est une destination rêvée, même si elle accuse un retard considérable en matière d'infrastructures d'accueil. Derrière cette hospitalité, se cachent néanmoins des frictions ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Infrastructure universitaire à Ghardaïa - Hadj Daoud, Aïssa (El Watan, 2008)
En effet, cette nouvelle structure est d'un grand secours dans la mesure où elle a permis à beaucoup d'étudiants, notamment ceux en lettres arabes, sociologie, psychologie, histoire, droit et ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Affrontement entre citoyens à Berriane (El Watan, 2008)
Le FFS met en garde contre toute sous-estimation de la situation La fédération du FFS de Ghardaïa met en garde les autorités contre toute sous-estimation des graves incidents que ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Les commerçants de Ghardaïa en colère - M. M. (El Watan, 2008)
Répondant à l'appel de leur union locale, les commerçants de Ghardaïa ont baissé, hier, les rideaux de leurs boutiques. La ville a été paralysée. Raison : les commerçants et artisans de ...
Keywords: Fekhar, Kamel Eddine (1963-2019)

Aller à Djerba et vouloir y rester - Sanschagrin, Dali (Le Droit, 2008)
Keywords: Tourisme -- Djerba

Cinq bonnes raisons pour aller à Djerba - Sanschagrin, Dali (Le Soleil, 2008)
Keywords: Tourisme -- Djerba

Des milliers de fidèles à Djerba pour le pèlerinage annuel de la Ghriba (AFP, 2008)
Keywords: Judaïsme -- Djerba

معالم على طريق الوحدة والألفة بين المسلمين - الأطرش, يحيى (البصائر, 2008)
Keywords: Tolérance religieuse -- Ibadisme

المشهد الجنائزي في جزيرة جربة في العصور القديمة من خلال مثالي السوق القبلي ومرقان - بن طاهر, سامي (الحياة الثقافية, 2008)
Keywords: Archéologie -- Djerba

موقع ميننكس- هنشير القنطرة- جربة - درين, علي (الحياة الثقافية, 2008)
Keywords: Archéologie -- Djerba

Les ibadites à l'origine de l'islamisation du Maghreb - Grim, Nordine; Rey, Pierre-Philippe (El Watan, 2008)
Keywords: Ibadisme -- Influence

L'an prochain à Djerba. Une communauté en plein essor - Beaugé, Florence (Le Monde, 2008)
Keywords: Judaïsme -- Djerba

Les Djerbiens à l’assaut du marché algérien (Maghreb confidentiel, 2008)
Keywords: Commerce -- Djerba

Pèlerinage de La Ghriba, Ferveur et liesse - Thabet, Fatah (Le Temps, 2008)
Keywords: Judaïsme -- Djerba

rencontre avec un potier tunisien - Grosbois, Nicole (teranga, 2008)
Keywords: Artisanat -- Djerba

الجامع الكبير بمدينة توزر أو جامع بلد الحضر: دراسة تاريخية معمارية - بوترعة, جهينة (الحياة الثقافية, 2008)
Keywords: Architecture -- Tozeur

دراسات في العصر الوسيط في الجزائر والغرب الإسلامي - عمارة, علاوة (سلسلة الكتب الأساسية في العلوم الإنسانية والإجتماعية, 2008)

نفحات الرحمن في رياض القرآن - كعباش, محمد بن سعيد (جمعية النهضة, 2008)
Keywords: Coran -- Commentaires -- 2000-....

نفحات الرحمن في رياض القرآن - كعباش, محمد بن سعيد (جمعية النهضة, 2008)
Keywords: Coran -- Commentaires -- 2000-....

Le vocabulaire berbère commun kabyle et mozabite : étude de lexicologie berbère comparée - Nouh, Abdallah (Université Mouloud Mammeri, 2008)
Keywords: Linguistique -- Mzab

Gigthi - Drine, Ali (Agence de mise en valeur du Patrimoine et de Promotion Culturelle, 2008)
Keywords: Antiquité

سليمان الباروني ودوره في الحركة الوطنية الليبية بين عامي 1905-1940 ف - عوض, صالح علي (جامعة عمر المختار, 2008)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Ibadisme et islamisation du Maghreb - Prevost, Virginie (Islamisation et arabisation de l’Occident musulman médiéval (VII e -XII e s.), 2008)

Parcours de femmes : Moufida Tlatli, Ingrid Sinclair et Nadine Labaki (Africultures, 2008)
Le 20 mai sur le Pavillon des Cinémas du Sud au Festival de Cannes 2008, Serge Toubiana, Directeur Général de la Cinémathèque Française et Bouchra Khalili, réalisatrice, qui dirige la Cinémathèque de Tanger, ont animé une table ronde réunissant à l’occasion des 40 ans de la Quinzaine des Réalisateurs Moufida Tlatli (Tunisie), Ingrid Sinclair (Zimbabwe)Lire la suite
Keywords: Cinéma -- Djerba

Les bains d'Alger durant la période ottomane, XVIe-XIXe siècles - Cherif-Seffadj, Nabila (Presses de l'Université Paris-Sorbonne, 2008)
Keywords: Emigration -- Mzab -- Algérie

العميل الأمريكي المنسي .. سلطنة عمان و السلطان كابوس - الصهيل (www.ekhlaas.org, 2008)
Keywords: Relations -- Oman -- Etats-Unis

مناهج التجديد لدى فقهاء عمان المعاصرين وأثره في التقنين الفقهي - باجو, مصطفى بن صالح (أعمال ندوة تطور العلوم الفقهية - التقنين والتجديد في الفكر الإسلامي المعاصر, 2008)

Murex Shells as Raw Material : The Purple-Dye Industry and Its By-products : Interpreting the Archaeological Record - Alberti, Maria Emanuela (Kaskal, Rivista di storia, ambienti e culture del Vicino Oriente Antico, 2008)
Keywords: Archéologie -- Djerba; Murex -- Djerba

الوكالة البريطانية في مسقط .. مكانتكا السياسية ومكامكا اإلدارية واالقتصادية 1899-1914 - الفياض, مقدام عبد الحسن باقر (مجلة آداب الكوفة, 2008)

Review of The Emergence of States in a Tribal Society: Oman under Sa‛id bin Taymur, 1932-1970 - Ochsenwald, William (The American Historical Review, 2008)
Keywords: Recension

Review of In the Shadow of the Ancestors: The Prehistoric Foundations of the Early Arabian Civilization in Oman - Magee, Peter (American Journal of Archaeology, 2008)
Keywords: Recension

Review of Oman: The Islamic Democratic Tradition - Allen, Jr, Calvin H. (International Journal of Middle East Studies, 2008)
Keywords: Recension

جهود فهرسة مخطوطات وادي ميزاب: رؤية وصفية ونقدية - بن دريسو, مصطفى بن محمد (الملتقى الوطني الثالث للمخطوطات : البحث العلمي ودوره في خدمة التراث المخطوط, 2008)
Keywords: Bibliothèques -- Mzab; Catalogue -- Mzab; Manuscrits -- Mzab

Le sultanat d'Oman - Ferreira, Mireille (La revue de Teheran, 2008)

الاشعاع الفكري في عهد الاغالبة والرستميين خلال القرنين 2-3هـ/8-9م - عليلي, محمد بن محمد (جامعة أبي بكر بلقايد, 2008)

معالم الحضارة الاسلامية بوارجلان ورقلة من نهاية الدولة الرستمية إلى زوال سدراتة - بوعصبانة, عمر بن لقمان (مديرية الثقافة, 2008)

فكر الخوارج والشيعة في ميزان أهل السنة والجماعة - الصلابي, علي محمد (دار ابن حزم, 2008)
Keywords: Religions comparées

مآثر الأصحاب انطباعات من زيارة الجزائر ووادي ميزاب في الفترة من 14 الى 24 ربيع الثاني 1429هـ الموافق له: من 20 الى30 ابريل 2008م - العبري, علي بن هلال (2008)

I giuristi šafi‘iti nel sultanato di Zanzibar - Declich, Lorenzo (Religione e politica: mito, autorità, diritto, 2008)
Keywords: Fiqh; Zanzibar

الحياة العلمية في جبل نفوسة وتأثيراتها على بالد السودان الغربي خلال القرون 2-8 حتى 8-14م - كوردي, محمود حسين (تاوالت, 2008)
Keywords: Vie intellectuelle -- Djebel Nefousa

奴隷言説の現在 : ザンジバルにおける奴隷制とアフリカ系オマーン人の歴史認識 = An Analysis of Discourses on Slavery : Slavery in Zanzibar and the Historical Perception of African Omanis - Okawa, Mayuko (Journal of Asian and African Studies, 2008)
Keywords: Esclavage -- Zanzibar

The Self Representation of The Imamate of Oman: the processes of construction of the list of imams - Matsuo, Masaki (2008)
As written in pamphlets issued by Arab Information Center in New York, the number of Ibadhi imams of Oman, who, according to allegations made by delegations of Arab countries in the United Nations, had ruled over Oman as legitimate rulers, was 61. Although it created an ostensive image on the historical reality of the Imamate of Oman, this number was a kind of invention of the Cairo office of the government-in-exile of the Imamate. This number related in pamphlets of Arab Information Center was based on information supplied by the Cairo office, which had made a list of imams with some authentic features from non-authentic French material, a Genealogical table of Zambaur. Some contradictory elements to the history legitimating the Imamate were altered and such alternations were concealed, Zambaur’s genealogical table was changed into the authentic material with plausible features as if being based on Salimi, a great Omani historian. This list could be recognized not a forgery but a result of self-representation of the Imamate of Oman without resource of discourse.
Keywords: Imamat -- Oman

Le Conseil d'Oman, une instance bicamérale de consolidation de l'autoritarisme sultanien - Valeri, Marc (Revue internationale de politique comparée, 2008)
Depuis 1996, le sultanat d’Oman dispose d’un parlement bicaméral, le Conseil d’Oman, composé d’une chambre haute, le Conseil d’état, nommée intégralement par le sultan, et d’une chambre basse, le Conseil Consultatif, élue au suffrage universel tous les quatre ans. Ce texte s’interroge sur le rôle de cette institution, dans un pays gouverné depuis 1970 par un souverain (Qabous Al Said) qui a su concilier un développement économique et social sans précédent avec la personnalisation du pouvoir la plus élaborée de toute la Péninsule arabique.
Keywords: Vie politique -- Oman -- 1970-2020

الحركة الإصلاحية في منطقتي الزيبان وميزاب بين سنتي 1920و 1954 - قوبع, عبد القادر (جامعة الجزائر, 2008)
Keywords: Réformisme -- Mzab

لقاءات في الفكر والدعوة - الخليلي, أحمد بن حمد (وزارة الأوقاف والشؤون الدينية, 2008)

الصورة الفنية في شعر بن عرابة العماني - سلوم, داود (وزارة التراث القومي والثقافة, 2008)
Keywords: Poésie -- Oman

رحلة الكابتن فلوير 1876 عبر الساحل في نهاية عهد الحكم العماني مع ملحق الأحداث التاريخية - Floyer, Ernest Ayscoghe (الفرات للنشر والتوزيع, 2008)
Keywords: Récits de voyage -- Oman

القضايا الوطنية والعربية الإسلامية من منظور أعلام مزاب 1902م - 1962م - بن عمر, موسى بن بكير (جامعة الجزائر, 2008)

الغشري من خلال قصائد ديوانه - الفلاحي, أحمد (نزوى: مجلة فصلية ثقافية, 2008)

Etude du système ancestral de captage et de distribution des eaux dans l’oasis de Ghardaia - Khelifa, Ali (Université Kasdi Merbah, 2008)

Sauvegarde des tissus anciens à travers la réhabilitation des maisons traditionnelles cas de la vallée du M'Zab - Khodja, Ali M. (Conférence Internationale sur la Médina Tlemcen, 13 et 14 mai 2008, 2008)
Les villes traditionnelles en Algérie qu'il soit médina ou ksour ont été conçues pour répondre à un contexte historique, social, économique et culturel spécifique à une époque et une région données. L'évolution dans le mode production, le mode de vie ainsi que les besoins croissants des habitants des centres historiques, ont pour conséquence la transformation de ce cadre bâti et les maisons traditionnelles en sont la première victime. Il suffit de noter l'aspiration des habitants de ces centres à habiter dans les quartiers nouveaux. Ceci est dû, d'une part, à l'insatisfaction de leurs besoins en matière d'espace habitable et l'inadéquation des espaces traditionnelles (surfaces et aménagement) avec le mobilier moderne. D’autre part, à l'évolution des structures sociales et la recomposition de la famille avec le temps ce qui a entraîné des modifications dans les pratiques sociospatiales dans les maisons traditionnelles. Notre objectif est d'arriver à cerner la problématique relative à l'adaptation des maisons traditionnelles au mode de vie moderne et essayer d'atteindre une stratégie de sauvegarde des villes anciennes, à travers la sauvegarde et la réhabilitation des maisons qui constituent en fait leur cellule de base. Notre étude porte sur la maison traditionnelle au niveau de la vallée du M'Zab. On s'intéresse à la configuration spatiale initiale de ces maisons et le mode de vie qui y correspondait, ainsi qu'à l'évolution des pratiques des habitants et leurs conséquences sur le cadre bâti et la menace que cela représente sur un patrimoine classé par l'UNESCO. Nos conclusions notent la remise en cause partielle du modèle traditionnel à travers l’introduction de nouveaux espaces et éléments architecturaux, ce qui donne lieu à un nouveau modèle hybride mi-traditionnel et mi-moderne.
Keywords: Urbanisme -- Mzab

Lewicki Tadeusz - Zaborski, Andrzej (Dictionnaire des orientalistes de langue française, 2008)
Keywords: Biographies; Biographies -- Pologne

إسهامات الشيخ أمحمد اطفيش الجزائري (ت1332هـ/1914م) في ميدان العلوم - الحاج موسى, بشير بن موسى (المؤتمر الدولي الأول في تاريخ العلوم عند العرب والمسلمين, 2008)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

« Terre d’encens » le Musée maritime du Sultanat d’Oman - Le Cour Grandmaison, Bruno (2008)
Keywords: Musée -- Oman

مساهمة القطاع السياحي في تحقيق التنمية المستدامة -دراسة حالة ولاية غرداية- - باز, الجيلالي (جامعة قاصدي مرباح, 2008)
Keywords: Tourisme -- Mzab

التناص مع القرآن الكريم في شعر مفدي زكرياء - بوعلي, عبد الناصر (الأثر - مجلة الآداب واللغات, 2008)
Keywords: Poésie -- Mzab

Un Controverso Episodio Della Storia Omanita Moderna: L'attacco Alla Spedizione Inglese Alle Miniere Di Şūr - Coppola, Anna Rita (Rivista degli studi orientali, 2008)
Keywords: Relations -- Oman -- Royaume-Uni

Conflicts and Harmony in Zanzibar - Mathews, Nathaniel (2008)
Finished Ali Muhsin Al Barwani's memoirs today-- Conflicts and Harmony in Zanzibar Sheikh Ali translated the Holy Quran into Swahili, a co...
Keywords: Zanzibar

Slaves, Pearls and the British in the Gulf in the Late Colonial Time - Zdanowski, Jerzy (Hemispheres, 2008)
Keywords: Esclavage -- Oman

التشكيل الغني في شعر إبراهيم أبي اليقظان - ركبة, فضيلة (جامعة منتوري, 2008)
Keywords: Poésie -- Mzab

„William Astor Chanler (1867-1934) und Ludwig von Höhnel (1857-1942) und Afrika“ - Kotrba, Franz (Universität Wien, 2008)
Keywords: Zanzibar

Etude des systèmes traditionnels de captage des eaux et d’irrigation dans les oasis de la vallee de M’zab: cas des oasis de Metllili, el Ateuf, Guerrara, Beni Izguene, Berriane et Bounoura - Guemari, F. (Université Kasdi-Merbah, 2008)
Keywords: Agriculture -- Mzab

Ibadi ahadith (Hajarmulder's Blog, 2008)
Ibadi Islam is mainly found in Oman and also in some places of eastern African countries like Somalia, further in Algeria, Tunisia and Libya. Ibadism’s founding figures are Jabir ibn Zayd and…
Keywords: Hadith

British missions around the Gulf, 1575-2005: Iran, Iraq, Kuwait, Oman - Arbuthnott, Hugh; Clark, Terence; Muir, Richard (Global Oriental, 2008)

Zanzibar - Goldman, Helle V. (New Encyclopedia of Africa, 2008)

De la vallée du M'zab à… Oman Cheikh Tfayech (1818-1914) Exégète, historien, poète, encyclopédiste - Tahri, Hamid (El-Watan, 2008)
Keywords: Biographies; Biographies -- Mzab -- 19e siècle

Décret n° 2008-42 du 2 janvier 2008, portant approbation de la révision du plan d’aménagement urbain de la commune d’Ajim du gouvernorat de Médenine - Ben Ali, Zine El Abidine (Journal officiel de la République tunisienne, 2008)
Keywords: Urbanisme -- Djerba

سماحة الشيخ أحمد بن حمد الخليلي مفتي عام سلطنة عُمان في مدينة يفرن النفوسية (2008)
Keywords: Relations -- Djebel Nefousa -- Oman

New Data on the Late Pleistocene of the Shakshuk Area, Jebel Gharbi , Libya - Mutri, Giuseppina; Lucarini, Giulio (The African Archaeological Review, 2008)
Le Jebel Gharbi constitue la limite septentrionale du haut plateau tripolitain dont l’élément le plus significatif est son imposant escarpement qui, orienté au nord fait face à la plaine côtière de la Gefara. Depuis les années 90, la Mission Archéologique Italo–Libyenne dans le Jebel Gharbi, dirigée par Barbara Barich (Université de Rome « La Sapienza »), a entrepris un projet de recherche à long terme, destiné à l’élaboration de la séquence culturelle de la région. Pendant la campagne de fouilles 2000, une importante zone de sédentarisation, caractérisée par différents niveaux d’occupation anthropique et de nombreux matériels archéologiques a été reconnue immédiatement aux pieds du Jebel, à proximité du village actuel de Shakshuk, entre la plaine de la Gefara et les dépôts alluvionnaires. Ces réserves d’eau pérennes ont permis l’occupation du territoire même pendant les phases plus arides du Pléistocène.
Keywords: Archéologie -- Djebel Nefousa

Mutations de la société, de l’espace nomade et du commerce caravanier dans le Sud-Est tunisien à la fin du XIXe siècle - Laroussi, Kamel (الجنىب الشرقي، حاضر وتاريخ, 2008)
Keywords: Nomadisme -- Djerba

الحركة الإباضية في المغرب الإسلامي من بداية القرن 2ه الى عاية إمامة عبد الرحمان بت رستم 160ه - عوشاش, جمال (جامعة الحاج لخضر, 2008)
Keywords: Ibadisme -- Histoire

أوضاع اليهود منطقة وادي ميزاب خلال القرن (13هـ/19م) - ثابت, جميلة; بيشي, رحيمة (المركز الجامعي بغرداية, 2008)
Keywords: Judaïsme -- Mzab

A Lion in the Path of Oman's Nationalization: Insurgency in Oman from the 1950s through the 1970s Examined through Social Movement Theory: - Howk, Jason (Defense Technical Information Center, 2008)
Keywords: Vie politique -- Oman -- 1932-1970

Die Ibaditen und der Oman: eine Fallstudie - Sarmini, Jasmin (Universität Wien, 2008)
Keywords: Ibadisme -- Oman

‘Unnatural and Ever Prejudicial’: Constructions of Race and Colonial Hierarchies by British Observers in 19th Century Zanzibar - Dyer, Jeffery (Georgetown University, 2008)
Keywords: Zanzibar

نمط القيادة في المجتمع الميزابي: دراسة ميدنية لتجار مدينة عنابة - طوراوي, منيرة (جامعة ناجي مختار, 2008)
Keywords: Emigration -- Mzab -- Algérie

واقع البيئة الحضرية في وادي مزاب دراسة حالة ومقارنة بين مدينة غرداية، بني يزقن والعطف - تزبينت, نور الدين; بوعزة, بهلول; قربوعي, بلقاسم (جامعة منتوري, 2008)
Keywords: Urbanisme -- Mzab

Sasanian Presence and Late Iron Age Samad in Central Oman, some Corrections - Yule, Paul A. (2008)
The question arises as to the nature of Parthian and Sasanian presence in south-eastern Arabia. Important is the role of the archaeological record in Oman in the early first millennium CE. The excavator has emended his chronology for late pre-Islamic Oman, de-emphasizing the evidence of radiocarbon dating. Recently in prominent places, Derek Kennet ignored and denigrated key results won from excavation and study in the 1990s. By means of the selective citing of sources, he concludes that the Samad cultural assemblage predates the first century CE.
Keywords: Archéologie -- Oman

The trans-Saharan slave trade, abolition of slavery and transformations in the North African Regency of Tunis, 1759-1846. - Montana, Ismael Musah (York University, 2008)
Keywords: Esclavage -- Tunisie

سلك الدرر الحاوي غرر الأثر: الجامع لعلوم الأديان و الأحكام و الأخلاق و الآداب - السيابي, خلفان بن جميل (وزارة التراث والثقافة, 2008)
Keywords: Fiqh

The Jebel Akhdar War: The Royal Air Force in Oman - Dye, Peter (Air Power Review, 2008)
Keywords: Dhofar

Pour une anthropologie de la libération ? - Rey, Pierre-Philippe (Nouvel Organon Inaliénable et Réflexif, 2008)

Scheich Uways b. Muḥammad al-Barāwi – Eine Qādir -igāza für den Sultan von Sansibar - Pleyer, Ruth (Universität Wien, 2008)
Keywords: Zanzibar

Retour à Dieu de frère Pierre (Sources vives, 2008)

Algeria: Floods in Ghardaia (Information bulletin of the International Red Cross and Red Crescent Movement, 2008)
Keywords: Inondations -- Mzab -- 2008

Kulturlandschaftsschutz und soziokulturelle Transformation im Tal des M'zab (Algerien) - Schmitt, Thomas M. (Geographische Rundschau, 2008)

Protection du patrimoine culturel et transformation socioculturelle : la "vallée du M'zab" un site classé patrimoine mondial en Algérie - Schmitt, Thomas M. (Les pays du Maghreb. Contributions de la géographie humaine allemande, 2008)
Keywords: Monuments -- conservation -- Mzab

‏المعجم الأمازيغي الوظيفي:‏ ‏العربية الأمازيغية = Amawal Amazig̳ amsg̳an : Taʻrabt - Tamazig̳t /‏ - مبارك, الأرضي (الأرضي مبارك, 2008)
Keywords: Linguistique -- Mzab

Les Rustamides (761-909) - Y.B. (www.qantara-med.org, 2008)
Keywords: Dynastie rustumide

جهود علماء ليبيا في علم الفقه خلال القرنين التاسع والعاشر الهجرين الخامس عشر والسادس عشر الميلادين - عطيوة, سعاد أبوالعيد علي (جامعة الجزائر, 2008)
Keywords: Fiqh; Fiqh -- Libye -- 15e siècle

Annual Jewish Pilgrimage Proceeds Peacefully - Godek, Robert F. (US Embassy, 2008)
Keywords: Judaïsme -- Djerba

Oman, the Land of No Jihad - McCants, Will (2008)
Ekhlaas member al-Suhayl observes that JIhadis criticize Saudi Arabia, Kuwait, Qatar and other Arab countries for collaborating with the United States, but they say nothing about Oman. Moreover, Oman
Keywords: Vie politique -- Oman -- 1970-2020

مدخل إلى التمييزِ العنصري في سلطنة عمان - آل تويه, سالم (اليوم أمس معصرن والقبيلة الصنم المعبود, 2008)
Keywords: Tolérance religieuse -- Oman

Ghardaïa-Algérie Tafilelt: La ville nouvelle inspirée de la ville millénaire (Euromed Heritage, 2008)
Keywords: Urbanisme -- Mzab

York graduate student works to save Algerian archival material - Daddi Addoun, Yacine (Newswire, 2008)
Keywords: Manuscrits -- Mzab

Une enfance dans M'Zâb de Abderrahmane Zakad. Éditions Alpha, Alger, 2008, 226 pages. (L'Expressiondz, 2008)
Keywords: Recension

Les premieres explorations arabes du Congo d'après une source omanaise: Le "Juhaynat al-Aẖbār fī Tarīẖ Zinjibār" de Sa'īd Bin 'Alī al-Muġīrī - Luffin, Xavier (Annales Aequatoria, 2008)
Les historiens s'intéressant à l'arrivée des premiers Arabes et Swahilis en Afrique centrale sont largement tributaires des sources occidentales, ou alors des témoignages arabes et swahilis recueillis et suscités par les Européens au 19e et au 20e siècle. Un chapitre du Juhaynat al-aẖbār fī tarīẖ Zinjibār, un imposant livre à propos de la présence arabe en Afrique rédigé par l'Omanais Sa'īd bin 'Alī al-Muġīrī à la fin des années 1930, nous livre la vision omanaise de l'arrivée des premiers Arabes et Swahilis dans l'est du Congo. Le présent article propose une traduction de ce chapitre et une confrontation des informations qu'il contient avec les sources européennes et africaines recueillies à l'époque coloniale et postcoloniale. The sources at the disposal of the historians dealing with the first arrival of the Arab and Swahili traders in Central Africa are mainly Western sources, or African testimonies recollected by Westerners in the 19th and 20th centuries. A chapter of the Juhaynat al-aẖbār fī tarīẖ Zinjibār, written in the late 1930 by Sa'īd bin 'Alī al-Muġīri, gives us the Omani point of view about these events. In this article, I intend to offer a translation of the text and to compare it with the information given by the European sources as well as the African testimonies collected during the colonial and post colonial periods.
Keywords: Relations -- Oman -- Congo

Review : Muhammad al-Mahruqi (ed.), Mugamir 'umani fi adgal Ifriqya. Hayat Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1905), al-ma'riif bi-TibuTib [Un aventurier Omanais au coeur de l'Afrique. La vie de Hamad bin Muhammad bin Jum'a Al-Murjabi (1840-1900), connu sous le nom de Tippo Tip], Cologne, Al-Kamel, 2006 (210 p.). - Luffin, Xavier (Annales Aequatoria, 2008)
Keywords: Recension; Tippo Tip (1837-1905)

East Africa - Hoffman, Valerie J. (The Islamic World, 2008)

The archaeology of Early Islamic Trans-Saharan Trading towns in West Africa: a comparative view and progressive methodology from the entrepot of Essouk-Tadmekka - Nixon, Sam (University College London, 2008)
Keywords: Archéologie -- Mali

ملامح الآداة التفسيرية في النص القرآني - سيوسيو, صالح بن بكير (جامعة الجزائر, 2008)

Oman et les Emirats arabes unis - Krebs, Bruno (Gallimard, 2008)

45 milliards de dinars pour effacer toutes les traces des inondations - Azzoug, Samir (La Tribune, 2008)
Keywords: Inondations -- Mzab -- 2008

En visite dans la wilaya, Abdelaziz Bouteflika déclare : «On a mobilisé les institutions de l’Etat» pour Ghardaïa - Azzoug, Samir (La Tribune, 2008)
Keywords: Inondations -- Mzab -- 2008

Stranger's notebook: poems - Stone, Naomi (Northwestern University Press, 2008)
A collection of poems that features a stranger who arrives at an ancient community that is both at home and estranged on the island. It tells how the people occupy the uneasy space of all insular communities, deciding when to let the world in and when to shut it out. It describes the daily lives of the Jews of Djerba and the Muslims next door
Keywords: Judaïsme -- Djerba

العلاقة بين الفقهاء و الإمامة الإباضية في عمان 132-280هـ / 749-893م :دراسة تاريخية - الصمادي, عبد الحميد حسن (جامعة آل البيت, 2008)
Keywords: Imamat -- Oman

الاختيارات النحوية للشيخ محمد بن يوسف اطفيش في " تيسير التفسير " - الصوافي, سالم بن مسعود (جامعة اليرموك, 2008)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Coran -- Commentaires -- 19e siècle

القواعد الفقهية عند الإباضية من خلال كتاب (منهج الطالبين و بلاغ الراغبين للشيخ الشقصي) - العميري, إبراهيم بن سليمان (جامعة آل البيت, 2008)
Keywords: Fiqh

مناقشات محمد بن يوسف اطفيش للزمخشرى فى "تيسير التفسير" دراسة بلاغية وتقويم - بسيونى, عبد الفتاح فيود (جامعة الازهر, 2008)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Coran -- Commentaires -- 19e siècle

منهج الشيخ اطفيش فى تفسيره المسمى(تيسير التفسير) - عجيبة, احمد على (جامعة الازهر, 2008)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914); Coran -- Commentaires -- 19e siècle

Berber chief Sulayman al-Barūnī: from prisoner to statesman - Sievert, Henning (Turkey 1908-1914: biographical approaches, 2008)
Keywords: Bārūnī, Sulaymān al- (1870-1940)

Zanzibar city - Sheriff, Abdul Mohamed Hussein (New Encyclopedia of Africa, 2008)

Barghash Ibn Saʿid (1833-1888) - Sheriff, Abdul Mohamed Hussein (New Encyclopedia of Africa, 2008)
Keywords: Biographies -- Zanzibar

The Azd migrations reconsidered: narratives of Amr Muzayqiya and Malik b. Fahm in historiographic context - Ulrich, Brian (Proceedings of the Arabian Seminar, 2008)

Constructing al-Azd: tribal identity and society in early Islamic centuries - Ulrich, Brian (University of Wisconsin-Madison, 2008)

From Tribe to Class: The Origins and the Politics of Resistance in Colonial Libya - Ahmida, Ali Abdullatif (Africa: Rivista trimestrale di studi e documentazione dell’Istituto italiano per l’Africa e l’Oriente, 2008)
Keywords: Italie -- colonies

The Portrayal of the East Vs. the West in Lady Mary Montagu's "Letters" and Emily Ruete's "Memoirs" - Rawi, Ahmed K. al- (Arab Studies Quarterly, 2008)
Keywords: Zanzibar

Zawawi, Omar bin Abd al-Munim - Allen, Jr, Calvin H. (Biographical Encyclopedia of the Modern Middle East and north Africa, 2008)
Keywords: Biographies

Al Bu Sa‘id, Qaboos (1940-) - Allen, Jr, Calvin H. (Biographical Encyclopedia of the Modern Middle East and north Africa, 2008)
Keywords: Biographies -- Oman

Les circoncellions. Un mouvement ascétique itinérant dans l’Afrique du Nord des IVe et Ve siècles - Pottier, Bruno (Antiquités africaines, 2008)
This article re-examines the circumcelliones phenomenon, notably concerning their origins, their nature and the interpretations of their actions in Numidia during the 340’s. The agonistici, as they call themselves, seem to originate from donatist groups devoted to voluntary martyrdom from as early as 315. Circumcelliones were wandering ascetics from the first half of the fourth century, as it was shown in the book by a donatist bishop of Rome, Macrobius, devoted to the asceticism of confessores and virgins, and in the Contra Gaudentium of Augustine. The agonistici, as ascetics and martyrs, challenged the donatist bishops’ authority. Their actions can be interpreted as a kind of usurped ecclesiastical jurisdiction against those who they defined as pessimi homines. These people were publicly struck by rods which were called Israel. The circumcelliones formed a new Christian rural elite in Numidia, a region organized by imperial and private estates, which were infrequently promoted to city status.
Keywords: Donatisme

In the ruins of Bahla: reconstructed forts and crumbling walls in an Omani town - Limbert, Mandana E. (Social Text, 2008)
Keywords: Moeurs et coutumes -- Oman

The sacred date: gifts of God in an Omani town - Limbert, Mandana E. (Ethnos, 2008)
Keywords: Moeurs et coutumes -- Oman

Moufida Tlatli - Fischbach, Michael (Biographical Encyclopedia of the Modern Middle East and North Africa, 2008)
Keywords: Biographies -- Djerba -- 20e siècle

Les circoncellions: Formation d'une élite rurale monastique autonome dans l'Afrique du Nord des IVe e Ve siècles - Pottier, Bruno (Revolte und Sozialstatuts von der Spaetantike bis zur fruehen Neuzeit, 2008)
Keywords: Donatisme

"Fantastic Charities": The Transformation of "Waqf" Practice in Colonial Zanzibar - Oberauer, Norbert (Islamic Law and Society, 2008)
Keywords: Zanzibar

The meanings of Timbuktu - Jeppie, Shamil; Diagne, Souleymane Bachir (HSRC Press, 2008)

L'influence du tourisme sur l'architecture et l'urbanisme : l'île de Djerba - Ben Yahia, Mehdi (ENSA Paris-La Villette, 2008)
Keywords: Tourisme -- Djerba

A Vision of Oman: State of the Sultanate Speeches by Qaboos Bin Said, 1970–2006 - Kechichian, Joseph Albert (Middle East Policy, 2008)
Keywords: Vie politique -- Oman -- 1970-2020

Al Bu Sa‘id, Badr bin Hamad bin Hamood - Jones, Jeremy (Biographical Encyclopedia of the Modern Middle East and north Africa, 2008)
Keywords: Biographies -- Oman

Min Tārīkh Jarba al-ḥadīth : Maʿalim wa Dhākira (Madrasat Sīdī Ibrāhīm al-Jumnī) - Jumnī, Muḥammad al-Hādī al- (Dār Tūnis lil-Nashr, 2008)
Keywords: Sidi Ibrahim al-Jumni, mosquée (Houmt Souk, Djerba)

Oases settlements in Oman - Gangler, Anette (Ed. Esefeld & Traub, 2008)

Oman : between independence and colonial control 1970-1976 - Worrall, James (University of Leeds, 2008)
The British government's announcement of its intention to withdraw 'East of Suez' by the end of 1971 was the catalyst for renewed efforts to resolve many disputes in the Gulf region. Accordingly, the threat posed by the growing Marxist inspired rebellion in Dhofar to Britain's remaining interests in the area could not be left unchallenged. But the means by which this challenge was to be met (including the extent of both overt and covert support for the Sultan) in the post-Suez era, posed a number of challenges for decision-makers in Whitehall. It soon became apparent that with aid flowing to the rebels from South Arabia, the situation was rapidly deteriorating. The failure of the counter-insurgency campaign thus far was increasingly seen to be the fault of Sultan Sa'id bin Taimur whose stubborn refusal to engage in anything but repression in Dhofar and whose denial of modernity to his people in spite of increasing oil revenues meant that Sa'id came to be seen as part of the problem and not the solution. This thesis examines how officials in London defined British interests in Oman and the debates in Whitehall, under successive governments, about how best to tackle the growing insurgency. This complex balancing act between protecting British interests and influence, creating an effective indigenous administration and security bodies while maintaining the image of strategic retreat and the sovereign independence of Oman forms the focus of this thesis. Through an exploration of British government decision making regarding Oman this thesis provides a systematic re-examination of the Anglo-Omani relationship during the critical years of transformation from isolated, undeveloped state into a modern outward looking nation. Since there have been no impartial, in-depth studies of this period which have had access to a wide range of primary source documents, the thesis is able to fill a gap in the literature by demonstrating how British interests were decided upon, how foreign policy was made and how it was implemented. Through the examination of this process this thesis aims to develop a better understanding of how and why Britain decided to commit herself to the protection of the Omani regime, while, at the same time, withdrawing from the Gulf and seeking membership of the European Economic Community. Using historical methodology and drawing extensively upon newly released archival records and interviews with former officials and high ranking officers, the thesis challenges established narratives regarding Britain's role in Oman. By examining the three key pillars of British support for the Sultanate of Oman - the political, military and diplomatic - this thesis argues that the evolution of a careful, considered and sometimes parsimonious policy marked British policy towards Oman, a policy far removed from the deterministic, callous and rapacious account presented by writers such as Halliday, Newsinger and Owtram.
Keywords: Vie politique -- Oman -- 1970-2020

Ranking suitable sites for Soil Aquifer Treatment in Jerba Island (Tunisia) using remote sensing, GIS and AHP-multicriteria decision analysis - Anane, Makram; Kallali, Hamadi; Jellali, Salah; Ouessar, Mohamed (International Journal of Water, 2008)
The present study aims to locate and rank suitable sites for Soil Aquifer Treatment (SAT) in Jerba Island (South Tunisia) by integrating a single-objective AHP method into a GIS model. The methodology represents a first step in SAT basin construction projects before field investigations. It considers several criteria related to technical, environmental and cost aspects. The result showed that a large area, covering 1489 ha, is suitable for SAT, which exceeds the required area to infiltrate the total treated wastewater produced by all the island wastewater plants. Being situated inside agricultural areas and near coastlines, potential sites for SAT could increase groundwater availability for irrigation and also mitigate existing marine intrusion problem facing Jerba aquifer. The best sites are found closer to Aghir plant than the rest of island WWTPs.
Keywords: Géologie -- Djerba

Mosquée à Djerba. Tunisie - Perregaux, Aloys (2008)
MOSQUÉE À DJERBA, TUNISIE L’île de Djerba, en dehors de la zone hôtelière, recèle des trésors cachés, notamment de très aniennes mosquées. Pour dessiner celle de Faldoun, Aloys Perregaux a mêlé, sans y paraître, divers points de vue, en se déplaçant. On a ainsi une vue synthétisée que la photo ne peut réaliser.
Keywords: Fadhloun, mosquée (Midoun, Djerba)

Tunisian Synagogues Flourish Though the Jews have Gone - Luxner, Larry (Middle East, 2008)
Keywords: Judaïsme -- Djerba

Djerba – «utenfor verden» - Grøthe, Johnny (Den Norske Tannlegeforenings Tidende, 2008)
Keywords: Judaïsme -- Djerba

Tunisie: des milliers de pèlerins juifs font la fête à la Ghriba (2008)
Keywords: Judaïsme -- Djerba

Pèlerinage de la Ghriba: vieux rites juifs perpétués dans la joie à Djerba (2008)
Keywords: Judaïsme -- Djerba

Milliers de juifs au pèlerinage à la Ghriba sous haute protection (2008)
Keywords: Judaïsme -- Djerba

Salam-shalom de la ghriba 2008 - Tibi, Nadine (harissa.com, 2008)
Keywords: Judaïsme -- Djerba

Destroying Mumiani : Cause, Context, and Violence in Late Colonial Dar es Salaam - Brennan, James R. (Journal of Eastern African Studies, 2008)
This article examines and contextualizes a riot that occurred in Dar es Salaam in 1959, in the peri-urban neighbourhood of Buguruni. The riot involved accusations that security guards and police were abducting neighbourhood residents and killing them in order to use their blood for the preparation of magical medicines. Those who abducted Africans for this purpose were popularly termed mumiani. Their rumoured existence is examined in the wider context of Dar es Salaam’s rapid urbanization, its peri-urban politics and land conflicts, and its systems of law and knowledge. The article also explores the many possible interpretations of this riot. Drawing on interviews with local residents, court testimonies, official correspondence, newspaper accounts, and colonial memoirs, the article constructs a historical account of the riot’s location, Buguruni, as well as a narrative of the riot itself and the subsequent legal actions. Such a violent event raises questions about the relationship between historical evidence and causality, as well as questions about contextualizing major events that fit awkwardly into prevailing historical narratives.
Keywords: Zanzibar

Swahili Cosmopolitanism in Africa and the Indian Ocean World, A.D. 600–1500 - LaViolette, Adria (Archaeologies, 2008)
Coastal peoples who lived along the Eastern African seaboard in the first millennium A.D. onwards began converting to Islam in the mid-eighth century. Clearly rooted in and linked throughout to an indigenous regional Iron Age tradition, they created a marked difference between themselves and their regional neighbors through their active engagement with Islam and the expanding Indian Ocean world system. In this paper I explore three ways in which interrelated cultural norms—an aesthetic featuring imported ceramics, foods, and other items, Islamic practice, and a favoring of urban living—created and maintained this difference over many centuries. These qualities of their identity helped anchor those who became Swahili peoples as participants in the Indian Ocean system. Such characteristics also can be seen to have contributed to Swahili attractiveness as a place for ongoing small-scale settlement of Indian Ocean peoples on the African coast, and eventually, as a target for nineteenth-century Arab colonizers from the Persian Gulf. This paper examines the archaeology of these aspects of Swahili culture from its early centuries through ca. A.D. 1500.
Keywords: Archéologie -- Zanzibar

Ishāmāt al-Shaykh AMuḥ. Iṭfayyish al-Jazā’irī (t. 1332 H./1914 M.) fī Maydān al-ʿUlūm - Ḥājj Mūsà, Bashīr b. Mūsà al- (al-Mu’tamar al-Duwalī al-awwal fī Tārīkh al-ʿUlūm ʿinda ‘l-ʿArab wa’l-Muslimīn, 2008)
Keywords: Atfiyyash, Muhammad b. Yusuf (1821-1914)

al-Munāẓarāt bayna ‘l-Ibāḍiyya al-Wahbiyya wa’l-Firaq al-ukhrà bi-Bilād al-Maghrib khilāla ‘l-Qarnayni al-thālith wa’l-rābiʿ/al-tāsiʿ wa’l-ʿāshir - Ḥasan, Muḥammad b. Mūsà (al-Madhāhib al-Islāmiyya bi-Bilād al-Maghrib min al-Taʿaddud ilà ‘l-Waḥda, 2008)
Based (mainly) on: Barrādī: al-Jawāhir al-Muntaqāt; Bārūnī, Sul.: al-Azhār al-Riyāḍiyya; Darjīnī: Ṭabaqāt; Masākanī, Abū Ḥafṣ ʿAmrūs b. Fatḥ: Uṣūl al-Daynūna al-Ṣafiya; Ibn al-Ṣaghīr: Akhbār al-A’imma al-Rustamiyyīn; Ibn Sallām: K. fīhi Bad’ al-Islām; Shammākhī: Siyar; Ṭālibī 1978; Warjlānī: K. al-Sīra wa-Akhbār al-A’imma; Wisyānī: Siyar al-Wisyānī.
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-

Īrādāt wa-Maṣrūfāt Imāmat al-Khalīlī li’l-ʿĀm 1363-4/1944-5, Wilāyat Biddiyya Namūdhajan - Yaḥmadī, Ibrāhīm (Jarīdat al-Waṭan, 2008)

De l’intérêt des sources archivistiques tunisiennes et françaises pour l’étude de l’histoire libyenne contemporaine - Lissir, Fethi (Revue d'Histoire Maghrébine, 2008)
Keywords: Archives -- France; Archives -- Tunis

Mawqif Ṣiḥāfat Ṭarāblus al-Gharb fī ‘l-ʿAhd al-ʿUthmānī min al-Taghalghul al-Istiʿmārī fī ‘l-Maghrib al-ʿArabī - Nuṣayrī, ʿAbd al-Razzāq Aḥmad al- (Revue d'Histoire Maghrébine, 2008)
Keywords: Journalisme -- Djebel Nefousa

La libia nelle scienze umane in Italia. Limiti dell’etnologia - Ouanès, Moncef (Revue d'Histoire Maghrébine, 2008)

Les particularités du mihrab chez les ibadites maghrébins - Prevost, Virginie (Acta Orientalia Belgica, 2008)
Keywords: Architecture -- Djerba

baʿīdan ʿan Zinjibār: ḥawla Mudhakkirāt al-Amīra al-ʿArabiyya al-Sayyida Sālima bint Saʿīd b. Sulṭān al-Būsaʿīdī - Khaḍīr, Ḍiyā’ (نزوى: مجلة فصلية ثقافية, 2008)
Keywords: Zanzibar

al-Ghishrī min khilāl Qaṣā’id Dīwānihi - Fallāḥī, Aḥmad b. ʿAbdallāh (نزوى: مجلة فصلية ثقافية, 2008)
Keywords: Poésie religieuse omanaise

Remarques sur le recueil ibadite-wahbite Siyar al-masa’ih : retour sur son attribution - Amara, Allaoua (Al-Andalus Magreb, 2008)
Keywords: Prosopographie -- Afrique du Nord

From another world! A possible Būyid origin of the decorated Miḥrāb of Central Oman? - Bandyopadhyay, Soumyen (Intercultural relations between South and Southwest Asia: studies in commemoration of E.C.L. During Caspers (1934 - 1996), 2008)
Keywords: Archéologie -- Oman

Textual sources on an Islamic African past: Arabic material in Zanzibar’s National Archive - Bang, Anne K. (The meanings of Timbuktu, 2008)
Keywords: Zanzibar

Poesia religiosa tradizionale in Nordafrica. I: I poemetti religiosi ibaditi. - Brugnatelli, Vermondo (2008)
On pp. 11-13, the first of the two Berber poems of Abū Fālgha (Jabal Nafūsa, first half 19th c.). On pp. 16-25, the Berber poem of Shaʿbān al-Qannūshī (Ziane, not far from Ghīzen at Jerba, end 18th c.).
Keywords: Linguistique; Poésie

Mulāḥaẓāt ḥawla Sikkat Nuqūd al-Fihriyyīn wa’l-Khawārij bi-Ifrīqiyya (128-142 H./745-759 M.) fī Ḍaw’ Majmūʿa Jadīda - ʿAṭā Allāh, Saʿīd ʿAbd al-Fattāḥ (Mishkāt: Al-Majalla al-Miṣriyya li’l-Āthār al-Islāmiyya, 2008)
Keywords: Numismatique

العزابة ودورهم في المجتمع الإباضي بميزاب - اسماوي, صالح بن عمر (مطبعة الفنون الجميلة, 2008)
Keywords: Vie religieuse -- Mzab

قبسات من انوار البدر الزاهر - الشيباني, سلطان بن مبارك (2008)
Keywords: Biographies -- Oman

Makānat Samā’il al-Fikriyya wa’l-Adabiyya - Salīmī, Maḥmūd b. Mubārak al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Vie intellectuelle -- Oman

al-Maʿālim al-Athariyya li-Wilāyat Samā’il - Mudaylawī, ʿAlī b. Rāshid al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Archéologie -- Oman

al-ʿĀdāt wa’l-Taqālīd fī Wilāyat Samā’il - Hāshimī, Sulaymān b. Sayf al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Moeurs et coutumes -- Oman

Samā’il wa-Makānatuhā al-Thaqāfiyya wa’l-Ijtimāʿiyya fī ‘l-Tārīkh al-Qadīm wa’l-Muʿāṣir - Hāshimī, Mubārak b. Sayf b. Saʿīd al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)

Jughrāfiyat Wilāyat Samā’il - Balūshī, ʿAlī b. Saʿīd al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005, 2008)
Keywords: Géographie -- Oman

Wilāyat Samā’il fī ʿAṣr al-Nahḍa - Bakrī, Khalfān b. Sulṭān al- (Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005., 2008)

Samā’il ʿabra ‘l-Tārīkh, al-. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī Wilāyat Samā’il Yawmay al-Ithnayn wa’l-Thulāthā’ 10 wa-11 Dhū ‘l-Qaʿda al-muwāfiq 12 wa-13 Dīsimbir 2005 - Muntadà al-Adabī al- (Ministry of National Heritage and Culture, 2008)

Qurayyāt fī ʿAṣr al-Nahḍa - Jahḍamī, Muḥammad b. Sayf (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)

Wilāyat Qurayyāt: Khaṣā’iṣ al-Mawḍiʿ wa’l-Imkāniyyāt al-Siyāḥiyya - Ḥatrūshī, Sālim b. Mubārak al- (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)

al-Mawrūthāt al-Shaʿbiyya fī Qurayyāt, al-ʿĀdāt wa’l-Taqālīd - Daramkiyya, ʿĀ’isha bint Ḥamad al- (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)

al-Ḥayāt al-Fikriyya li-Wilāyat Qurayyāt - Baṭṭāshī, Aḥmad b. Khālid (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)
Keywords: Vie intellectuelle -- Oman

al-Makāna al-Tārīkhiyya li-Wilāyat Qurayyāt - Akhzamī, Saʿīd b. Sālim al- (al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006, 2008)
Keywords: Oman -- Histoire

al-Qurayyāt ʿabra ‘l-Tārīkh. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī’l-Fatra min 4-5 Dhū ‘l-Ḥijja 1427 H. al-muwāfiq 25-26 Dīsimbir 2006 - Muntadà al-Adabī al- (Ministry of Heritage and Culture, 2008)

عمرو النامي: مسية عطاء.. ِفي درب الخير - الشيباني, سلطان بن مبارك (مكتبة الأنفال, 2008)
Keywords: Ennami, Amr (1939-198X)

al-Shaykh Muḥammad b. Shāmis al- Baṭṭāshī Faqīhan - Siyābī, ʿAbdallāh b. Rāshid al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)
Keywords: Biographies; Biographies -- Oman

al-Jawānib al-Tārīkhiyya fī Mu’allafāt al-Shaykh al-Baṭṭāshī - Kindī, al-Khaṭṭāb b. Aḥmad al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)

Qirā’a fī Kitāb Salāsil al-Dhahab li’l-ʿAllāma al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī - Dardīrī, al-Ṭāhir Muḥammad al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)

al-Shaykh Muḥammad b. Shāmis al- Baṭṭāshī: Ḥayātuhu wa-Aʿmāluhu - Baṭṭāshī, Ḥārith b. Muḥammad al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)
Keywords: Biographies -- Oman

Faqīh al-Shuʿarā’ wa-Shāʿir al-Fuqahā’: al-Baṭṭāshī Shāʿiran - Bakkā’, Muḥammad Kāẓim al- (Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007, 2008)
Keywords: Poésie -- Oman

Qirā’āt fī Fikr al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Iḥtifā’an bi-Dhikrà al-Shaykh Muḥammad b. Shāmis al-Baṭṭāshī 5-6 Jum. I 1428 al-muwāfiq 21-22 Māyū 2007 - Muntadà al-Adabī al- (Ministry of Heritage and Culture, 2008)

Tārīkh Ṣuḥār al-Siyāsī wa’l-Ḥaḍārī min Ẓuhūr al-Islām ḥattà Nihāyat al-Qarn al-rābiʿ al-Hijrī - Mundhirī, Muḥammad b. Nāṣir b. Rāshid al- (Dār al-ʿUlūm al-ʿArabiyya, 2008)

الاباضية في ميدان الحق - المسقري, ناصر بن مطر (مكتبة الأنفال, 2008)
Keywords: Ibadisme -- thèmes et motifs

Adawāt Kitābat al-Makhṭūṭāt fī ‘l-Bī’a al-ʿUmāniyya - Rābiḥī, Muḥammad al-; Ḥarrāṣī, Nabhān al- (Makhṭūṭāt al-ʿUmāniyya, al-: kayfa waṣalat ilaynā. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawm al-ithnayn 15 Jumādà ‘l-ūlà 1427 H. al-muwāfiq 12 Yūnyū 2006, 2008)
Keywords: Manuscrits -- Oman

al-Ṭuruq al-mustakhdama fī Kitābat al-Makhṭūṭ al-ʿArabī wa-Zakhrafatihi wa-Tajlīdihi - Ḥajjī, Khalfān b. Zahrān al- (Makhṭūṭāt al-ʿUmāniyya, al-: kayfa waṣalat ilaynā. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawm al-ithnayn 15 Jumādà ‘l-ūlà 1427 H. al-muwāfiq 12 Yūnyū 2006, 2008)
Keywords: Manuscrits -- Conservation

al-Naskh wa’l-Tadāwul - Balūshī, Ibrāhīm b. Ḥasan al- (Makhṭūṭāt al-ʿUmāniyya, al-: kayfa waṣalat ilaynā. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawm al-ithnayn 15 Jumādà ‘l-ūlà 1427 H. al-muwāfiq 12 Yūnyū 2006, 2008)

al-Makhṭūṭāt al-ʿUmāniyya : Kayfa waṣalat ilaynā. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī Yawm al-ithnayn 15 Jumādà ‘l-ūlà 1427 H. al-muwāfiq 12 Yūnyū 2006 - Muntadà al-Adabī al- (Ministry of Heritage and Culture, 2008)
Keywords: Manuscrits -- Oman

al-Ṣirāʿ al-Madhhabī bi-Ifrīqiya ilà Qiyām al-Dawla al-Zīriyya - Majdūb, ʿAbd al-ʿAzīz al- (Dār Saḥnūn, 2008)

al-Khawarij, reality or legend? - Mazrui, Juma Muhammad Rashid al- (2008)
Keywords: Kharijisme

Rester le même tout en devenant un autre : les "islamistes" tunisiens exilés en France - Ayari, Michaël Béchir (Maghreb-Machrek, 2008)
Keywords: Emigration -- Djerba -- France

Al-Ṣaḥīfa al-qaḥṭānīya - Ibn Ruzayq, Ḥumayd Ibn Muḥammad (Dār al-Bārūdī li-ṭ-Ṭibāʿa wa-'n-Našr, 2008)
Keywords: Sources -- Oman

Tārīkh ʻUmān al-siyāsī - Ṭāʼī, ʻAbd Allāh Muḥammad (Sharikat al-Rubayʻān, 2008)

La structuration des ibadites-wahbites au Maghreb (XIe-XVe siècle) - Amara, Allaoua (Annales Islamologiques, 2008)

الامام جابر بن زيد امام المذهاب الاباضي: امير حركة اسلامية سياسية معارضة - حواري, محمد بن حامد (دار الضياء, 2008)

Nawāfidh ʿalà Tārīkh Nafzāwa - Ḍayf Allāh, Muḥammad (al-Maghāribiyya li’l-Ṭibāʿa, 2008)
Keywords: Ibadisme -- Nefzaoua; Nefzaoua -- Histoire

Qarīban min aš-šams: ḥiwārāt fi 'ṯ-ṯaqāfa al-ʿūmānīya - Fārisī, ʿAbd al-ʿAzīz al-; Maʿmarī, Sulaymān al- (Muʾassasat al-Intišār al-ʿArabī, 2008)

Die Reformbewegung in der neuzeitlichen Ibāḍīya: Leben, Werk und Wirken von Muḥammad b. Yūsuf Aṭfaiyaš 1236 - 1332 h.q. (1821 - 1914) - Ourghi, Abdel-Hakim (Mitteilungen zur Sozial- und Kulturgeschichte der islamischen Welt, 2008)

Oman, 1965 - Wilkinson, John Craven (Oman and the Trucial states, 2008)
Keywords: Récits de voyage -- Oman

Āl Hāshim al-Rustāqiyyūn wa-Makānatuhum al-ʿIlmiyya - Kharūṣī, Muhannā b. Khalfān b. ʿUthmān al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

Lamaḥāt Manhajiyya wa-Adabiyya fī Mu’allafāt al-Aṭibbā’ Āl Hāshim: al-Ṭabīb Rāshid b. ʿUmayra Namūdhajan - Khāliṣ, Walīd Maḥmūd (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

Qirā’a fī thalāthi Qaṣā’id Ṭibbiyya Makhṭūṭa li’l-Shaykh al-Ṭabīb Rāshid b. ʿUmayra b. Thānī “al-ʿAynī” al-Rustāqī al-ʿUmānī min Āl Hāshim - ʿIbrī, Ḥusayn al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

al-Taṭbīqāt al-Ṭibbiyya fī Mu’allafāt Rāshid b. ʿUmayra al-Rustāqī - Hinā’ī, ʿAlī b. Ṭālib b. ʿAlī al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

Qirā’a fī K. Fākihat Ibn al-Sabīl li’l-Ṭabīb Rāshid b. ʿUmayra b. Thānī al-ʿAynī al-Rustāqī al-ʿUmānī - Fārisī, ʿAbd al-ʿAzīz al- (Aʿlām al-Ṭibb fī ʿUmān fī ‘l-Qarnayni al-tāsiʿ wa’l-ʿāshir al-Hijriyyayni, min. Ḥiṣād al-Nadwa allatī aqāmahā al-Muntadà al-Adabī fī ‘l-Fatra min 7 wa-8 Muḥarram 1427 al-muwāfiq 6 wa-7 Fabrāyir 2006, 2008)

al-Ḥayāt al-Siyāsiyya wa’l-Iqtiṣādiyya fī Iqlīmay al-Baḥrayn wa-ʿUmān bayna ‘l-Qarnayni al-khāmis wa’l-sābiʿ al-Hijrī (al-ḥādī ʿashar wa’l-thālith ʿashar al-Mīlādī) - Āl Thānī, ʿAbdallāh Jāsim (Dār al-ʿUlūm al-ʿArabiyya li’l-Ṭibāʿa wa’l-Nashr, 2008)
Keywords: Vie politique -- Oman -- 11e siècle

Sur un nouveau manuscrit ibâḍite-berbère : La Mudawwana d’Abû Ġânim al-Ḫurâsânî traduite en berbère au Moyen Âge - Ould-Braham, Ouahmi (Études et Documents Berbères, 2008)
Keywords: Fiqh -- Libye -- 8e siècle; Linguistique -- Djebel Nefousa

The Ibāḍīs - Hoffman, Valerie J. (The Islamic World, 2008)

Uzi Rabi. The Emergence of States in a Tribal Society: Oman under Sa‘id bin Taymur, 1932–1970 .:The Emergence of States in a Tribal Society: Oman under Sa ʕ id bin Taymur, 1932–1970 - Ochsenwald, William (The American Historical Review, 2008)
Keywords: Recension

Uzi Rabi The Emergence of States in a Tribal Society: Oman under Saʿid bin Taymur, 1932–1970 (Portland, Ore.: Sussex Academic Press, 2006). Pp. 320. $67.50 cloth. - Riphenburg, Carol J. (International Journal of Middle East Studies, 2008)
Keywords: Recension

The Ibadhi Imamate of Muhammad bin ‘Abdallah al-Khalili (1920–54): The Last Chapter of a Lost and Forgotten Legacy - Rabi, Uzi (Middle Eastern Studies, 2008)
Keywords: Vie politique -- Oman -- 1970-2020; Vie politique -- Oman -- 20e siècle

The Emergence of States in a Tribal Society: Oman Under Sa'id bin Taymur, 1932-1970 : Uzi Rabi - Silverberg, Sanford R. (Digest of Middle East Studies, 2008)
Keywords: Recension

سلك الدرر الحاوي غرر الأثر: الجامع لعلوم الأديان و الأحكام و الأخلاق و الآداب - السيابي, خلفان بن جميل (وزارة التراث والثقافة, 2008)

Satan's Seven Specious Arguments: al-Shahrastānī's Kitāb al-Milal wa-l-niḥal in an Ismaʿili Context - Gaiser, Adam R. (Journal of Islamic Studies, 2008)
In light of recent evidence that indicates al-Shahrastānī's adherence to Nizari Ismaʿilism, this article highlights certain structural and thematic characteristics of al-Shahrastānī's Kitāb al-Milal wa-l-niḥal by comparing it to earlier (especially fourth/tenth-century) Khurasani Ismaʿili heresiographies such as Abū Tammām's Kitāb al-Shajara and al-Rāzī's Kitāb al-Zīna. Shared features of these works include the avoidance of specifically Ismaʿili language in the body of the work, utilization of neo-Platonic symbolism and language, and (for al-Shahrastānī and Abū Tammām) use of Satan (or satans) as the origin of sectarian differences among humankind. An awareness of these features will better allow scholars to contextualize al-Shahrastānī's work in relation to other heresiographies, and may point to the existence of a Khurasani Ismaʿili ‘school’ of heresiography. At the very least, the similarities show the influence of Abū Tammām's work on al-Shahrastānī. An awareness of al-Shahrastānī's Ismaʿili inspired methodology in his Kitāb al-Milal, in turn, challenges the prevalent scholarly view of al-Shahrastānī as an objective cataloguer of sectarian divisions.
Keywords: Hérésiographie -- Ismaélisme

سيرة العلامة سيف بن حماد بن أحمد الخروصي 1313-1379هـ - الخروصي, خالد بن عبد الله (المؤلفان, 2008)

الموجز في تاريخ عمان السياسي: في القرون الإسلامية الأولى، 1هـ-906هـ/ 622-1500م - فوزي, فاروق عمر (دار مجدلاوي, 2008)

موقف الإمامة الإباضية من الصراع القرمطي البويهي على عمان 287هـ/ 900م - 447هـ/ 1055م - الوهيبي, يوسف بن محمد (جامعة السلطان قابوس, 2008)

التفسير عند العوتبي من خلال كتابه الضياء - الحجري, ناصر بن محمد (جامعة الزيتونة, 2008)

دلائل الاعتقاد عند أهل الحق و الأستقامة - الريامي, عبد الله بن سليمان (مكتبة مسجد الاثلة العامة, 2008)

الإباضية في ميدان الحق :‏ ‏الطريق الصحيح لمعرفة الحقيقة، افتراءات كتاب المقالات على الإباضية، أسباب التعصب ضد الإباضية، مفاهيم يجب أن تختفي، أدلة استقامة الإباضية - المسقري, ناصر بن مطر (مكتبة الانفال, 2008)

طلعت الشمس: شرح شمس الأصول - السالمي, عبد الله بن حميد (مكتبة الامام السالمي, 2008)

معارج الآمال على مدارج الكمال بنظم مختصر الخصال - السالمي, عبد الله بن حميد (مكتبة الإمام السالمي, 2008)

تاريخ عمان :‏ ‏بين الماضي المجيد والحاضر السعيد - بديوي, يوسف علي (مكتبة الصفاء, 2008)

الإباضية في موكب التاريخ - معمر, علي يحيى (مكتبة الضامري, 2008)
Keywords: Monuments -- Djerba; Ouvrages de vulgarisation; Tîfarrûjîn, mosquée (Oualagh, Djerba)

إتحاف الأنام بشرح جوهر النظام - الخروصي, سعيد بن خلف (مطبعة عمان, 2008)

القواعد الفقهية بين التأصيل و التطبيق: بحوث ندوة تطور العلوم الفقهية في عمان خلال القرن الرابع الهجري: القواعد الشرعية أنموذجاً - ندوة تطور العلوم الفقهية (وزارة الأوقاف والشؤون الدينية, 2008)

طلعة الشمس :‏ ‏شرح شمس الأصول - السالمي, عبد الله بن حميد (مكتبة الإمام السالمي, 2008)

المختصر المفيد في الكفارات :‏‏ ‏مسائل في: الكفّارات المرسلة، الكفّارات المغلّظة، الكفّارات المختلف فيها - المعولي, المعتصم بن سعيد (جامعة السلطان قابوس, 2008)

أماكن انتشار المذهب الإباضي - الخليلي, أحمد بن حمد (رسائل الفكر و الهدى, 2008)

المختصر المفيد في الكفارات: مسائل في الكفارات المرسلة، الكفارات المغلظة، الكفارات المختلف فيها - المعولي, المعتصم بن سعيد (جامعة السلطان قابوس, 2008)

العزابة ودورهم في المجتمع الإباضي بميزاب - اسماوي, صالح بن عمر (مطبعة الفنون الجميلة, 2008)
Keywords: Vie religieuse -- Mzab

الرد على جميع المخالفين :‏ ‏الخوارج، المرجئة، المعتزلة - الوسياني, يغلا بن زلتاف (مكتبة الضامري, 2008)
Keywords: Foi -- Traité -- 10e siècle

تاريخ عمان السياسي - الطائي, عبد الله بن محمد (المكتبة الربيعان للنشر والتوزيع, 2008)

الأسر والذوات التونسية في القرن التاسع عشر بحث معمق في البنيات الاجتماعية والثقافية والاقتصادية والسياسية...مذيل بترجمات لثلاث أسر عاكسة للبنيات جميعا أسرة أحمد التليلي - أسرة النيفر - أسرة ابن عياد - خوالدية, الضاوي (2008)
Keywords: Famille Bin Ayyad

الإباضية في جبل نفوسة: دراسة الحياة الاجتماعية من خلال مخطوط " سير أهل نفوسة " لصاحبه مقرين البغوطوري - البخاري, محمد الشاذلي (كلية العلوم الانسانية والاجتماعية, 2008)

جربة مواقع و معالم وتراث - المرابط, عبد اللطيف (وزارة الثقافة والمحافة على التراث, 2008)

الحركة الإباضية ومساعيها لتأسيس الدولة - معروف, بالحاج بن بنوح (المواقف, 2008)

Die Ibādīya in der islamischen Häresiographie - Ourghi, Abdel-Hakim (Asiatische Studien, 2008)
Keywords: Hérésiographie -- Ibadisme

Djerba: Sites, Monuments and Heritage - Mrabet, Abdellatif (Agence de mise en valeur du Patrimoine et de Promotion Culturelle, 2008)
Keywords: Architecture -- Djerba; Monuments -- conservation -- Djerba

آراء الإمام محمد بن محبوب الكلامية - الوهيبي, مسلم بن سالم بن علي (مجلة التنوير, 2008)

نشاط الحركة المذهبية الخارجية ببلاد المغرب الإسلامي خلال القرن الرابع الهجري : ثورة أبي يزيد الخارجي نموذجا - بلهوارى, فاطمة (مجلة المواقف, 2008)
Keywords: Kharijisme

التاريخ السياسي لدولة الخواج الصفرية 140 - 366 هـ - عبد المعموري, محمد عبد الله (مجلة كلية التربية, 2008)

المعتزلة في الدولة الرستمية - أحمد, سلوى عبدالخالق علي (حوليات آداب عين شمس, 2008)
اهتمت الدراسة بتاريخ المعتزلة والدور الذى لعبته في الدولة الرستمية سياسياً واقتصاديا وفكرياً وإنهم لم كونوا مجرد فرقة كلامية عولت على العقل في تأسيسي علم التوحيد أو علم الكلام وحققوا إنجازات أخرى جد هامة خصوصا على الصعيد الثقافي إذا ناظر أصحاب المذاهب الأخرى وخصوصا الخوارج الأباضية وتفوقوا عليهم بدرجة جعلت المذهب الأباصي نفسه يتأثر بالاعتزال بدرجة أو بأخرى والمعتزلة كفرقة كلامية تميزت بإنتاج غزير في مجالات متعددة وقدموا دراسات جادة ومبتكرة وكان لهم دور محمود في نشر الإسلام ليس فقط بين البربر بل حتى في أفريقيا جنوب الصحراء من خلال نشاطهم التجاري مع تلك البلاد إلى جنوب اهتمامهم بوجود جيش قائم في أماكن متفرقة من المغرب الأوسط أما عن دورهم الاجتماعي عرف عنهم إقامة اعتبار للعريقة والعصبية والعنصرية وهو ما يتسق مع طبيعة البربر والمعتزلة كفرقة كلامية وإن تميزت أفكارها بالعديد من الجوانب الإيجابية، فيعاب عليهم غلوهم في الاعتقاد بخلق القران وتشددهم في فرض رأيهم على البسطاء من العامة. غير أن هذه الانتقادات لا تقلل من الأثر العظيم الذي خلفته المعتزلة في الفكر الإسلامي. فهي بحق ساعدت على تقدم علم الكلام وقدمت لنا فكرا عميقاً امتزج فيه الكلام بالفلسفة.
Keywords: Vie intellectuelle -- Rustumides

التطورات السياسية فى عمان - الدرويش, جاسم ياسين محمد (الوثيقة, 2008)
شهدت عمان في القرن الثاني الهجري / الثامن الميلادي قيام إمامة أباضية فيها، والإباضية إحدى فرق الخوارج أجمعت المصادر على أن تسميتها مشتقة من اسم عبد الله بن أباض التميمي الذي تزعم الجناح المعتدل من حركة الخوارج بعد الاختلاف مع نافع بن الأزرق عام 64ه/638م في البصرة حول شرعية الثورة ضد المسلمين المخالفين لمذهبهم، وقد تبنت الاباضية منذ ذلك الوقت آراء معتدلة حتى وصفت بأنها أقرب فرق الخوارج إلى أهل السنة، وقد انتهج الاباضية أسلوب التنظيم والعمل السري، إ ولاقت دعوتهم أرضا خصبة في عمان حتى نجحت في انتخاب أول إمام لها في عمان وهو الجلندي بن مسعود عام 132ه/749م، إلا إن ذلك لم يدم طويلاً إذ اعتبرت الخلافة العباسية قيام إمامة أباضية في عمان تهديدا خطيرا لزعامتها الدينية والدنيوية للمسلمين فأرسلت قواتها إلى هناك وتمكنت من إسقاط إمامة الجلندي عام 134ه/751م. إلا أن ذلك لم يأت بنتائج هامة بالنسبة للعباسيين إن استمر الناس في ولائهم للإباضية بسبب رسوخ المذهب الأباضي هناك، وما إن حل عام 177ه/793م حتى تمكنت الأباضية من توحيد صفوفها وانتخاب إمام لها وهو ومحمد بن أبي عفان مكونة بذلك الإمامة الاباضية الثانية في عمان والتي استمرت حتى عام 280ه/893م. وقد شهدت سبعينات القرن الثالث الهجري /التاسع الميلادي انقساماً خطيراً في صفوف الحركة الأباضية في عمان، ففي عام 272ه/886م عزل الإمام الصلت بن مالك الخروصي (237-272ه/851-886م) من الإمامة من قبل العالم السامي موس بن موسى (من بنى سامة بن لؤي بن غالب) بحجة شيخوخته ونصب مكانه راشد بن النظر، وعلى إثر هذا الحادث ثارت نار الحرب الأهلية في عمان بين الناصرين للصلت بن مالك وأغلبهم من القبائل اليمانية والمعارضين له وأغلبهم من القبائل الترارية ، نتج عنها هزيمة الترارية في وقعة القاع وقتل قائدهم موس بن موسى،، وعلى أثر ذلك توجه عدد من زعماء الترارية إلى الخلافة العباسية لمساعدتهم من أجل إرجاع النفوذ العباسي هناك، فكانت سلسلة من الحروب أدت إلى انهيار الإمامة الأباضية الثانية في عمان. إن في البحث محاولة لتسليط الضوء على فترة غامضة من تاريخ عمان أعقبت انهيار الإمامة عام 280ه/893م وذلك بسبب اضطراب النصوص التاريخية حولها وتضاربها رغم أهميتها، إذ شهدت قيام إمارة بنى سامة فيها، وأولى محاولات القرامطة لمد نفوذهم إليها.

صورة الشراة في شعر الخوارج - فليح, أحمد (دراسات - العلوم الإنسانية والاجتماعية, 2008)
يشيع في مصادر التأريخ وكتب الأدب القديمة مصطلح (الشراة)، علماً على الخوارج، من غير ما إشارة الى وجود فرق أو اختلاف في الدلالة بينهما. ولم يفطن دارسو الأدب ونقاده المعاصرون الى أي فرق يلحظ بين المصطلحين بل هم يذهبون الى أن شعر الخوارج لا يصور تفاصيل عقائدهم، لذا لم يعنوا بدلالات هذين المصطلحين. ومن ثم جار هذا الخلط على الحقيقية التاريخية، إذ لم تعن الدراسات القديمة والحديثة بالشراة إلا من خلال كونهم خوارج فحسب، فأخطأت الوقوع على (فئة) متميزة بمهامها وصفاتها، وأخطأت، من ثم، الوقوع على المعاني والدلالات الدقيقة لغير قليل من النصوص الخارجية التي تشير الى الشراة أو تصفهم وهي نصوص بالغة الندرة والجودة. \\ لقد قادت الملاحظة الدقيقة لمعاني مصطلح الشراة ودلالاته السياسية والدينية، وللمهام التي اضطلع بها الشراة، والصفات، التي تمدحوا بها ي شعرهم، الى تبين هذا الفرق بين (الشراة) و(الخوارج)، الذي يتمثل في أن الشراة فئة مختارة من بين أشداء الخوارج لتضطلع بمهام قتالية صعبة ومحددة بظرف طارئ، ويقترن اضطلاعها هذا بشروط وقواعد يلتزمون بها، وليس كل الخوارج على هذا النحو من الوصف؛ فمنهم قعدة وخارجون على السلطان حسب، ومنهم شراة. يؤيد هذا الفهم وصف الشراة أنفسهم بالفئة القليلة والعصابة، والعصبة والنفر، بل هم يحددون عددهم بعشرة شراة وبأربعين شارياً. والعدد أربعون بالغ الأهمية بين شروط (الشراء) في الفقه الخارجي. ثم جاءت من بعد نصوص الفقه الإباضي لتؤكد مصداقية هذا التفريق وهذا التصور لمهمة الشراة؛ إذ أصبح مسلكاً من مسالك المجتمع في الفقه الإباضي. \\ لقد كان لتحديد معنى الشراة وتبين مهامهم أثره في الفهم الدقيق لعقائد الخوارج ومبادئهم، وتبين أثر عقائدهم في شعرهم. \\ وقد اتبع البحث للوصول الى هدفه المنهج التأريخي (الاستردادي)، وهو يدرس الجوانب التاريخية من موضوع الشراة، ويتابع تطور فكرة الشراء، كما اتبع المنهج الاستقرائي، وهو يدرس النصوص الشعرية ويحللها. \\
Keywords: Poésie kharijite

القواعد الفقهية عند الإباضية: تنظيرا وتطبيقا - الراشدي, هلال بن محمد (جامعة الزيتونة, 2008)
Keywords: Fiqh

الفقه الأباضي في مرحلة التأسيس : المدونة نموذجاً وفي عهد النهضة والتجديد : الشيخان بيوض وبكلي نموذجين - الطالبي, عمار (أعمال ندوة تطور العلوم الفقهية - التقنين والتجديد في الفكر الإسلامي المعاصر, 2008)
Keywords: Bayyūḍ, Ibrāhīm ibn ʿUmar (1899-1981); Fiqh; Réformisme -- Mzab

اختصار المواريث والفرائض تأليف أبو عمار عبدالكافي الورجلاني الإباضي من علماء ق 6 هـ: دراسة وتحقيق - الهنائي, خليفة بن سيف بن حمد (جامعة الزيتونة, 2008)
Keywords: Fiqh -- traité -- 12e siècle

التآلف والتسامح بين الأديان والمذاهب جزيرة جربة أنموذجا - الصولى, علي بن محمد (أعمال ندوة التآلف والوئام بين الأديان والتحديات الثقافية الدولية الراهنة, 2008)
Keywords: Tolérance religieuse -- Djerba

أبناء جزيرة جربة في الحركة الوطنية 1881-1961 - الصغير, عميرة علية (مجلة روافد, 2008)
Keywords: Recension

الفقه الإباضي: نشأته ومصادره - خلف, عبد الجواد (الدار الدولية للإستثمارات الثقافية, 2008)
Keywords: Fiqh

معجم مصطلحات الإباضية: العقيدة، الفقه، الحضارة - بحاز, إبراهيم بن بكير; السالمي, عبد الرحمان; بابا عمي, محمد بن موسى (وزارة الأوقاف والشؤون الدينية, 2008)

صفات التكفيريين الخوارج: التحذير من التكفير - بيهي, سعيد بن محمد (دار اقرأ, 2008)
Keywords: Kharijisme

آخر الخوارج‏‏: ‏أشياء من سيرة صحافية‏ - الريس, رياض نجيب (رياض الريس‏ للكتب والنشر, 2008)
Keywords: Kharijisme

دراسة عن الفرق في تاريخ المسلمين‏: ‏الخوارج والشيعة - جلي, أحمد محمد أحمد (2008)
Keywords: Kharijisme

معلم وذاكرة: مدرسة سيدي ابراهيم الجمني - الجمني, محمد الهادي (دار تونس للنشر, 2008)
Keywords: الجمني، ابراهيم (1628-1721)

منهج الإباضية في معالجة الذات والصفات - سيدبي, جمال رجب (التفاهم, 2008)

L’impact du tourisme sur les structures socio-économiques et environnementales de Djerba : nouvelles dynamiques spatiales - Ajej, Imed (Université Paris 7, 2008)
Keywords: Tourisme -- Djerba

Die Spannungen der jüdisch-muslimischen Beziehung in Tunesien während des 20. Jahrhunderts und ihr Zusammenhang mit der massiven Auswanderung der Juden aus diesem Land - Nehdi, Dorsaf (Freien Universität Berlin, 2008)
Keywords: Judaïsme -- Djerba

Les entrepreneurs tunisiens: la difficile émergence d'un nouvel acteur social - Nabli, Rabah (Histoire et perspectives méditerranéennes, 2008)
Keywords: Commerce -- Djerba

Décret n° 2008-1673 du 22 Avril 2008, portant homologation des procès-verbaux de la commission de reconnaissance et de délimitation des terrains relevant du domaine privé de l'État du gouvernorat de Médenine (délégation de Djerba Midoun) (2008)
Keywords: Urbanisme -- Djerba

Arrêté du ministre de l'Équipement, Habitat et Aménagement du Territoire du 21 Février 2008, portant délimitation des zones requérant l'établissement du plan d'aménagement urbain de la zone de Sidi-Jmour - Cheikh Yahia de la commune de Djerba Ajim, gouvernorat de Médenine (2008)
Keywords: Urbanisme -- Djerba

Duveyrier Henri - Barthelemy, Guy (Dictionnaire des orientalistes de langue française, 2008)
Keywords: Biographies -- France

Goichon Amélie-Marie - Messaoudi, Alain; Sellès, Michèle (Dictionnaire des orientalistes de langue française, 2008)
Keywords: Biographies -- France

Masqueray Charlemagne Émile - Lefébure, Claude (Dictionnaire des orientalistes de langue française, 2008)
Keywords: Biographies -- France

Motylinski (Calassanti-Motylinski) Gustave Adolphe de - Lefébure, Claude; Messaoudi, Alain (Dictionnaire des orientalistes de langue française, 2008)
Keywords: Biographies -- France

Basset Marie Joseph René - Lefébure, Claude (Dictionnaire des orientalistes de langue française, 2008)
Keywords: Biographies -- France

Basset Henri - Lefébure, Claude (Dictionnaire des orientalistes de langue française, 2008)
Keywords: Biographies -- France

Abū Bayhas - Lewinstein, Keith (Encyclopaedia of Islam, 2008)
Keywords: Biographies

Abū ʿAmmār ʿAbd al-Kāfī b. Abī Yaʿqūb - Hoffman, Valerie J. (Encyclopaedia of Islam, 2008)
Keywords: Biographies

Jannāwunī, Abū Zakariyyāʾ al- - Salimi, Abdulrahman al- (Encyclopaedia of Islam, 2008)
Keywords: Biographies -- Djebel Nefousa; Jannāwunī, Yaḥyā b. al-Khayr

Les tribulations du commandant Chapuy dans les principautés arabes du Golfe dans la seconde moitié du XIXe siècle: Oman – Émirats – Qatar – Bahreïn - Koweït - Béguin-Billecocq, Xavier (Relations internationales et culture, 2008)
Keywords: Récits de voyage -- Oman

The Moors and the Portuguese: Sea charts and Navigational Skills - Agius, Dionisius A. (Continuity and change in the realms of Islam: studies in honour of Professor Urbain Vermeulen, 2008)
Keywords: Navigation -- Oman

Modern intellectual readings of the Kharijites - Timani, Hussam S. (American university studies, 2008)
Keywords: Kharijisme

L'affaire Jean de la Goutte : religieux et laïcs dans la diplomatie jésuite en Méditerranée (1553-1555) - Fabre, Pierre-Antoine (Le commerce des captifs : les intermédiaires dans l'échange et la rachat des prisonniers en Méditerraneée, XVe-XVIIIe siècle, 2008)

Scheich Muḥsin bin Zahrān al-ʻAbrī: tribale Macht im Oman des 19. Jahrhunderts - Hoffmann-Ruf, Michaela (Islamkundliche Untersuchungen, 2008)

Andrea Doria: un prince de la Renaissance - Graziani, Antoine-Marie (Tallandier, 2008)
Keywords: Invasions chrétiennes -- Djerba

1560 Cerbe Deniz Savaşinin Türk Ve İspanyol Tarihindeki Yeri - Akinci, Tunç (Université d’Ankara, 2008)
Keywords: Invasions chrétiennes -- Djerba -- 1560

The Makran-Baluch-African Network In Zanzibar And East Africa During The XIXth Century - Nicolini, Beatrice (Uncovering the History of Africans in Asia, 2008)
Keywords: Zanzibar

L'aventure ibāḍite dans le Sud tunisien: (VIIIe - XIIIe siècle) ; effervescence d'une région méconnue - Prevost, Virginie (Suomalaisen Tiedeakatemian toimituksia Humaniora, 2008)

Restructuration du quartier de Houmt-Souk Djerba - Ben Moussa, Chaouki (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2008)
Keywords: Architecture -- Djerba

Etude pour la construction d’un ouvrage de communication au niveau de la chaussée romaine entre la lagune de Boughrara et la mer méditerranée - Ayari, Mohammed; Allegue, Maher; Tlili, Iskander (Journées Nationales Génie Côtier - Génie Civil, 2008)
Keywords: Architecture -- Djerba

Mit der Waffe des Islams gegen Zionisten und Anthropomorphisten. Die politische Relevanz mittelalterlicher Theologie im ibāḍitischen Islam der Gegenwart - Berger, Lutz (Die Welt des Islams, 2008)
Starting from the polemics of the Ibāḍī mufti of Oman, Aḥmad al-Khalīlī, with Ibn Bāz and other Wahhābī 'ulamā' this paper addresses how representatives of contemporary Islam try to overcome sectarian differences and how they make sense of medieval theological precepts in a radically changed intellectual and political environment. The paper stresses the role of (invented traditions of) resistance against external and internal foes (imperialism and--to a lesser degree--Sufism) as ideological basis for modernist Islamic ecumenism. Remaining sectarian differences are explained by pretending that rival sects are in reality agents of external enemies of Islam. An example of this argumentation is Aḥmad al-Khalīlī's effort to remove the Wahhābīs from the fold of Islam by making Wahhābism a Jewish sect with Islamic trappings. For this purpose Aḥmad al-Khalīlī recycles premodern Ibāḍī polemic against the Sunnis at large. Medieval theologoumena are thereby given a present-day political meaning. Without openly attacking the Sultan, the mufti al-Khalīlī's arguments against the Wahhābīs can at the same time be read as a document of opposition against the Omani regime's policies, in a situation where the Sultanate is confronted by a resurgence of political Ibāḍism.

Le choix d'une vie sobre : témoignage des Ibadhites - Durand, Michel (En manque d'Eglise, 2008)
Ayant fait le choix de vivre à l'oued M'Zab, les Ibadhites avaient aussi pris conscience que le refus de l'ostentation était une garantie de sauvegarde. Origine VIIe siècle : Mohamed ne s'est pas désigné de successeur. Ali, son cousin et gendre, fut proclamé...
Keywords: Moeurs et coutumes -- Mzab

1560 Cerbe Deniz Savaşının Türk ve İspanyol tarihindeki yeri - Önalp, Ertuğrul (Ankara Üniversitesi, 2008)
Spain and Venice felt more and more threatened by the Ottomans and their corsair allies after losing against Barbarossa Hayreddin's Ottoman fleet at the Battle of Preveza in 1538 and the disastrous expedition of Emperor Charles V against Barbarossa in Algiers in 1541.Especially when Piyale Pasha had captured the Balearic Islands and together with Turgut Reis raided the Mediterranean coasts of Spain in 1558. Taking advantage of the piece made between Spain and France ;the initiative came from Maltese Knights who appealed to King Philip II of Spain to organize an expedition to retake Tripoli from Turgut Reis, who had captured the city from the Maltese Knights in August 1551 and had subsequently been made Bey (Governor) of Tripoli by Sultan Suleiman the Magnificent.The naval Battle of Djerba took place in May 1560 near the island of Djerba, Tunisia. It is believed by most reputable historians that the fleet assembled by the allied Christian powers in 1560 consisted of between 50 and 60 galleys and between 40 and 60 smaller craft. For instance , the official historian of the Knights of St John Giacomo Bosio, writes that there were 54 galleys. Fernand Braudel also mentions about 54 warships plus thirty-six supply vessels. Carmel Testa who had access to the archives of the Knights of St. John made more accurate listings. He lists precisely 54 galleys, 7 brigs, 17 frigates, 2 galleons, 28 merchant vessels and 12 small ships. These ships and their supplies were supplied by a coalition that consisted of Genoa, Naples, Sicily, Florence the Papal States, and the Knights of Saint John. Giovanni Andrea Doria, nephew of the Genoese admiral Andrea Doria, took the command of the fleet which assembles in Mesina. The fleet first sailed to Malta, where bad weather conditions and the hard sea forced it to remain for two months. Around 2,000 men were lost there, due to bad conditions and contagious diseases.Finally the fleet set sail for Tripoli on 10 February, 1560. Unfortunately we do not know the exact number of soldiers aboard. Braudel gives 10,000-12,000; Testa 14,000; considering the number of men a sixteenth century galley could carry, old figures like 20.000 are completely exaggerations.The expedition came to shore near to Tripoli but the lost of too many soldiers and the bad condition of the remaining soldiers changed the objectives. They decided to take Djerba first to use it as a command centre for the operation that was to made to Tripoli. Then the expedition returned to Djerba which they overran quickly. The Viceroy of Sicily, Don Juan de la Cerda, Duke of Medina Coeli, ordered the fort in the island to be strengthened.By that time Piyale Pasha was ordered to patrol in the Mediterranean and to sieged a small island of Malta, he learnt a Christian fleet occupied Djerba to occupy later Tripoli. The Turkish fleet changed it?s course and head to Djerba after taking necessary precautions. The fleet arrived at Djerba on 11 May 1560. Since the Christian forces did not expect it to come before July it was a complete surprise for them. With the help of the strong winds, Piyale Pasha had closed the Gap between Istanbul and Djerba in less then a month.The battle was over in a matter of hours, with about half the Christian galleys captured or sunk. Anderson gives the total number of Christian casualties as 18,000 but Guilmartin more conservatively puts the losses at about 9,000 of which about two-thirds would have been oarsmen.Giovanni Andrea Doria the commander of the fleet managed to escape in a small vessel and the remaining forces took refuge in the fort that they had strengthened just days earlier, which was soon attacked by the combined forces of Piyale Pasha and Turgut Reis. The garrison surrendered after a siege of three months and Piyale Pasha took the prisoners back to Istanbul, including the Spanish commander D. Alvaro de Sande, who had taken command of the Christian forces after Doria had escaped. The accounts of the final days of the besieged garrison are irreconcilable.The victory in the Battle of Djerba represented the apex of Ottoman naval domination in the Mediterranean. Soon The Ottomans made an unsuccessful effort on Malta in 1565, the new base of Saint Jean Knights who were expelled from Rodas. Although the Ottomans had captured Cyprus from Venice in 1571 the legend of the invincible Ottoman fleet continued until the Battle of Lepanto in 1571 where the Turkish naval forces were destroyed by the Christian fleet.Shortly after The Ottomans were able to build another large fleet in less than a year after Lepanto, and recaptured Tunis from the Spaniards and their Hafsid vassals in 1574.
Keywords: Invasions chrétiennes -- Djerba -- 1560

Une enfance dans le M'zab - Zakad, Abderrahmane (Editions Alpha, 2008)
Keywords: Littérature -- Mzab

T. F. Mitchell (1919-2007) and his Zuara Berber materials - Stroomer, Harry (Études et Documents Berbères, 2008)
Keywords: Linguistique -- Zouara

Retour à Ghardaïa - Amhis, Yacine (Entre deux rives. Exil et transmission, 2008)
Keywords: Judaïsme -- Mzab

L'autre Zanzibar: géographie d'une contre-insularité - Bernardie-Tahir, Nathalie (Hommes et sociétés, 2008)
Keywords: Zanzibar

Habitat semi collectif: Habitat semi étatique à Midoun. Djerba essai d’écriture d’une Architecture domestique - Cherif, Manel (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2008)
Keywords: Architecture -- Djerba

Centre International d’accueil des jeunes à Djerba : un espace d’échange autour de l’Artisanat Tunisien - Farhat, Olfa (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2008)
Keywords: Artisanat -- Djerba

Patrimoine : Sauvegarde, sensibilisation et éducation, quels liens possibles avec le tourisme de masse ; le cas de Djerba - Khalfa, Aurélia Louisa (Université Paris 1, 2008)
Keywords: Architecture -- Djerba; Tourisme -- Djerba

« Tourisme de Santé » clinique de chirurgie Esthétique à Djerba - Satouri, Rached (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2008)
Keywords: Tourisme -- Djerba

Mario Scalési, nouveau poète maudit. Perspectives comparatistes - Brunel, Pierre (Revue de littérature comparée, 2008)
Keywords: Littérature

Cap Nord - Bouraoui, Hédi (Les Editions du Vermillon, 2008)
Keywords: Littérature -- Djerba

Et Dieu créa Djerba la Douce - Ben Youssef, Slimane al-Amin (2008)
Keywords: Tourisme -- Djerba

Habitat adapté à l’île de Djerba - Hadj Taïeb, Massara (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2008)
Keywords: Architecture -- Djerba

Une Architecture éphémère: village de vacances à "Lella el Hadhria" Djerba - Mhaya, Wafik (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2008)
Keywords: Architecture -- Djerba

Village culturel à Houmt Souk à Djerba en Tunisie - Mosbahi, Chafia (ENSA Paris-Val de Seine, 2008)
Keywords: Architecture -- Djerba

La maison de l’Architecture à Djerba - Ouiriemmi, Malek (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2008)
Keywords: Architecture -- Djerba

Femmes mozabites et habitat à Guerrara (Algérie) : Etude sur l'adaptation culturelle à un nouveau type d'habitation - Benaïssa, Sarah (Université Paris 12, 2008)
Keywords: Architecture -- Mzab

D’une langue de contact entre berbères ibadites - Brugnatelli, Vermondo (Berber in contact: linguistic and sociolinguistic perspectives = Le berbère en contact: études en linguistique et sociolinguistique, 2008)
Keywords: Linguistique

Littérature religieuse à Djerba. Textes oraux et écrits - Brugnatelli, Vermondo (Oralité et nouvelles dimensions de l'oralité: intersections théoriques et comparaisons des matériaux dans les études africaines, 2008)
Keywords: Linguistique

Femme veuve : paria ou messie - Mrabet-Robana, Zakia (22e conférence mondiale d’études francophones, 2008)
Keywords: Moeurs et coutumes -- Djerba

Etude comparative de la qualité de deux huiles pétrolières de la région de Zarzis-Djerba ainsi que de leurs mélanges - Ben Haj Yahia, Marouen (Faculté Des Sciences de Tunis, 2008)

Caractérisation physico-chimique et étude de la valorisation du gaz naturel produit dans la région de Djerba et Zarzis - Khalf, Nadia (Faculté Des Sciences de Tunis, 2008)

Etude de corrélation des huiles pétrolières de la région de Zarzis-Djerba - Mediouni, Houda (Faculté des Sciences de Tunis, 2008)

L’île de Djerba. Tourisme, Environnement et Patrimoine - Bourgou, Mongi; Kassah, Abdelfattah (Cérès Editions, 2008)
Keywords: Tourisme -- Djerba

Diagnostic and membrane autopsy of Djerba Island desalination station - Boubakri, Ali; Bouguecha, Salah (Desalination, 2008)

Abundance and biomass of the ciliate community during a spring cruise in the Gulf of Gabes (Eastern Mediterranean Sea, Tunisia) - Aleya, Lotfi; Hannachi, Imen; Drira, Zaher; Hassen, Malika; Hamza, Asma; Ayadi, Habib; Bouain, Abderrahman (Acta Protozoologica, 2008)
We studied the spring spatial distribution of the ciliate community coupled with environmental factors along the coast and in the open sea at 30 stations sampled (between 27 May and 9 June 2006) in the Gulf of Gabes (Tunisia, Eastern Mediterranean Sea). A total of 61 taxa belonging to 36 genera and 5 taxonomic classes were identified. The ciliate assemblage was numerically dominated by spirotrichs (86% of total ciliates). This group is largely dominated by the choreotrichs (92%) among which tintinnids represented 99%. The total ciliates abundance showed a gradual decrease from the coastal area to the open sea and an increase from the surface to the bottom. The maximum abundance (400 cells l-1) and biomass (6.29 µgC l-1) were found in station 27, close to Djerba Island. The tinitinnid Rhabdonella spiralis was cosmopolitan, being found almost at every station and at each depth, while other taxa may be exclusive to the neritic area, others to the open sea area. The distribution of species in the Gulf of Gabes seemed most likely influenced by the combined effects of hydrographic conditions, zooplankton predation and urban interferences.
Keywords: Littoraux -- Djerba

Une tentative d’histoire de la ville ibadite de Sadrāta - Prevost, Virginie (Mélanges de la Casa de Velázquez, 2008)
Keywords: Ibadisme -- Sedrata

Meninx: The Luxury of the Purple Dye Industry and the Richness of Architecture - Morton, Thomas ([Convegno Internazionale Dedicato al Tema "Le Ricchezze dell'Africa, Risorse, Produzioni, Scambi"], 2008)
Keywords: Archéologie -- Djerba

Arquitectura púnica: los monumentos funerarios - Prados Martínez, Fernando (Anejos de A EspA, 2008)
Keywords: Archéologie -- Djerba

Témoignages archéologiques sur les activités halieutiques de Meninx - Drine, Ali (Ressources et activités maritimes des peuples de l'Antiquité: actes du colloque international de Boulogne-sur-Mer, 12, 13 et 14 mai 2005, 2008)
Keywords: Archéologie -- Djerba

les ports phéniciens et puniques géomorphologie et infrastuctures - Carayon, Nicolas (Université Strasbourg II, 2008)
Keywords: Archéologie -- Djerba

Lotophages - Desanges, Jehan (Encyclopédie berbère, 2008)
Keywords: Antiquité

L’occupation du sol à Rhizène à l’époque antique. Les données de la prospection - Ben Tahar, Sami (Revue des études phéniciennes-puniques et des antiquités libyques, 2008)
Keywords: Archéologie -- Djerba